Polyolefin-based microporous films by sequential cold and hot stretching of unannealed polypropylene copolymer films.

JP7644102B2Active Publication Date: 2025-03-11DDP SPECIALTY ELECTRONICS MATERIALS US LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022519544
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-16
Filing Date
2020-09-29
Publication Date
2025-03-11
Estimated Expiration
2040-09-29

Smart Images

  • Figure 0007644102000038
    Figure 0007644102000038
  • Figure 0007644102000039
    Figure 0007644102000039
  • Figure 0007644102000040
    Figure 0007644102000040
Patent Text Reader

Abstract

A microporous polymer film and a method for making the same are disclosed. The microporous polymer film comprises one or more polypropylene copolymers including one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, wherein the microporous polymer film comprises (i) a total amount of the polypropylene homopolymer chain segments of 50 to 82 wt %, based on the weight of the microporous polymer film, and (ii) a total amount of the one or more ethylene-containing copolymer chain segments of 18 to 50 wt %, based on the weight of the microporous polymer film, wherein at least a portion of the ethylene-containing copolymer chain segments comprise polymerized units of ethylene in an amount of at least 45 wt %, based on the weight of the ethylene-containing copolymer chain segments.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE Embodiments of the present disclosure relate generally to microporous films and their applications in a variety of end uses, such as house wraps, roof membranes, active and medical packaging, and hygiene and medical articles.

[0002] The present invention provides microporous polymer films derived from specific polypropylene (PP) copolymers that contain polypropylene homopolymer chain segments and ethylene-containing copolymer chain segments. The PP copolymer microporous films disclosed herein are produced without the traditional means of achieving porosity, i.e., inorganic fillers that create cavitation, perforations, or extensive pre-treatment to produce good crystalline morphology as is practiced for homopolymer polyolefins. annealing Instead, film porosity is achieved by the use of a specific type of PP copolymer to produce a non-porous film, followed by a sequential cold / hot stretching process that results in microphase separation induced pore formation in the polyolefin-based films disclosed herein. One advantageous feature of the method disclosed herein is that the non-porous film is not subjected to the cold / hot stretching process prior to the cold / hot stretching process. annealing No step required and even after cold / hot stretching process Heat Set or annealing The advantage is that no steps are required.

[0003] Described herein are compositions of PP copolymers and process steps and methods for making and using them.In particular, these microporous films can be made to provide moisture vapor permeability while maintaining an effective barrier against liquid water, and these permeabilities can be tailored.The balance of properties of the microporous films disclosed herein suggests that these films can find use in applications such as house wraps, roof membranes, and hygiene and medical articles, packaging (including active packaging and medical packaging) and filtration. [Background technology]

[0004] Described herein is a microporous film, its manufacturing method and its use. The present invention provides a cost-effective and environmentally benign way to produce microporous structures in polyolefin-based films by extrusion film casting / blowing and dry stretching processes. The pore size and porosity of these microporous films can be tailored to achieve optimized performance in various end-use applications (e.g., for house wrap applications, the films can be manufactured to have porosity and permeability properties equivalent to commercial products such as Tyvek house wrap from DuPont de Nemours, Inc., Wilmington, DE, USA). Instead, smaller pore size can provide a barrier against air moving through walls. According to the U.S. Department of Energy, up to 40% of the energy consumed to heat or cool a building is lost due to air leakage.

[0005] A variety of end-use applications require, or at least benefit from, the use of breathable films, which may be described as films that are relatively permeable to water vapor and relatively impermeable to liquids.

[0006] House wraps function as a weather resistant barrier, preventing rain from entering the wall assembly while allowing water vapor to pass to the outside. Therefore, to be effective, house wraps must be water repellent and have high water vapor transmission (permeability). Currently, house wraps can be categorized into two categories: woven and perforated, and nonwoven and nonperforated. Perforated wraps, which are generally less expensive, are made from polyethylene or polypropylene that have been microscopically perforated to make them permeable, while nonperforated wraps consist of a polyolefin layer that allows water vapor to pass through its nonwoven fibrous mesh. Current technology generally involves multiple steps for the manufacturing process.

[0007] In addition, the present invention provides a polyolefin-based microporous film for roof membrane application. There is a large market need for breathable roof membranes. Current non-permeable roof membranes made from polyvinyl chloride (PVC), thermoplastic polyolefins (TPO) or polymerized ethylene propylene diene monomer (EPDM) cannot meet this need, and polyolefin-based microporous films offer an opportunity to provide a low-cost alternative with high water vapor permeability compared to such current ones. The low / low water vapor permeability of current roof membranes leads to moisture accumulation under the roof membrane, causing delamination of the roof membrane from the roof (e.g., lightweight concrete structure) over time, and then failure of the roof structure. The higher water vapor permeability of thick polyolefin-based microporous films meets the important requirements of roof membranes, such as high water vapor transmission (permeability), e.g., 10 perms or more; and good water repellency (weather barrier). The weatherability of polyolefin-based microporous films can be further enhanced by applying anti-UV agents.

[0008] Polyethylene films are widely used in sanitary absorbent products, such as diaper backsheets. Diaper backsheets can be classified as breathable or non-breathable. Breathable backsheets typically use films filled with more than 50% CaCO3 (or other inorganic fillers) by weight and / or micro-voided. However, due to the vigorous competition in the sanitary absorbent product market, film manufacturers are required to seek differentiation techniques that allow for enhanced product performance, such as improved mechanical property performance, while also allowing for cost reduction, such as from further downgauging (thinner films). Summary of the Invention [Problem to be solved by the invention]

[0009] Thus, there is a need in many end use markets for improved breathable films that have a very thin gauge and high porosity to allow high water vapor transmission while preventing liquid water leakage and ensuring good processability and mechanical properties. The non-interconnected micropores of the microporous films disclosed herein provide better barrier performance against air, water, bacteria and blood, which is essential for house wrap, roofing membrane, air filtration, medical packaging and medical back table cover applications. The relatively high melting temperature of PP copolymers allows their application in steam sterilization related to medical packaging. The wide range of tunable breathability also suggests that these microporous films are also possible for active packaging (sachet) applications. Thus, there is a need for compositions containing the polypropylene copolymer compositions described herein, microporous films made therefrom, methods of preparing them and methods of using them. The invention disclosed herein is directed to these and other important objectives and provides a solution to these market needs. [Means for solving the problem]

[0010] In certain embodiments, the invention described herein provides a microporous polymeric film comprising, consisting of, or consisting essentially of one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the polypropylene homopolymer chain segments being in a total amount of 50 to 82 wt % based on the weight of the microporous polymeric film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymeric film, and (ii) ethylene-containing copolymer chain segments. and ethylene-containing copolymer chain segments in a total amount of 18 to 50 wt % based on the weight of the microporous polymer film or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segments, wherein at least a portion of the ethylene-containing copolymer chain segments contain polymerized units of ethylene in an amount of at least 45 wt % based on the weight of the ethylene-containing copolymer chain segments or at least 55 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segments.

[0011] In one embodiment, a method of forming a microporous polymeric film includes the method steps of: (a) one or more polypropylene copolymers, comprising: (i) one or more polypropylene homopolymer chain segments in a total amount of from 50 to 82 wt % based on the weight of the polypropylene copolymer or from 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer; and (ii) one or more ethylene containing copolymer chain segments in a total amount of from 18 to 50 wt % based on the weight of the polypropylene copolymer or from 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer. and (c) subjecting the non-porous film to successive cold and hot stretching steps, including (i) at least one cold stretching step at a temperature in the range of -20°C to 50°C, and (ii) at least one hot stretching step at a temperature in the range of 50°C to 150°C, thereby producing a microporous polymer film.

[0012] In some embodiments, the method is a continuous process for producing a microporous polymeric film. In particular, in some embodiments, the method does not include any additional steps after the formation of a non-porous film. annealing The process proceeds without any steps, and any subsequent steps after the formation of the microporous polymer film. annealingor Heat Set It proceeds without any steps and is a continuous process for producing microporous polymer films.

[0013] The accompanying drawings, which are included to provide a further understanding of the invention, and which are incorporated in and constitute a part of this specification, illustrate embodiments of the invention and, together with the description, serve to explain the principles of the invention. [Brief description of the drawings]

[0014] [Figure 1A] 1 shows mercury intrusion porosimetry data for Tyvek® housewrap. [Figure 1B] 1 shows mercury intrusion porosimetry data for PP C7054-07NA microporous films after a range of varying hot stretch conditions. [Figure 2A] FIG. 1 shows an SEM image of a film cross section of unstretched PP C7054-07NA film, indicated by the 20 micron scale bar. [Figure 2B] FIG. 1 shows SEM images of film cross-section of stretched PP C7054-07NA film after 25% cold stretch at 100 mm / sec (room temperature) and 50% hot stretch at 5 mm / sec (100° C.), indicated by the 20 micron scale bar. [Figure 2C] FIG. 1 shows SEM images of film cross-section of stretched PP C7054-07NA film after 25% cold stretch at 100 mm / sec (room temperature) and 50% hot stretch at 5 mm / sec (100° C.), indicated by the 5 micron scale bar. [Figure 3A] FIG. 1 shows an SEM image of the film surface of unstretched PP C7054-07NA film, indicated by the 20 micron scale bar. [Figure 3B] FIG. 1 shows an SEM image of the film surface of unstretched PP C7054-07NA film, indicated by the 10 micron scale bar. [Figure 3C]FIG. 1 shows SEM images of the film surface of stretched PP C7054-07NA film after 25% cold stretch at 100 mm / sec (room temperature) and 50% hot stretch at 5 mm / sec (100° C.), indicated by the 20 micron scale bar. [Figure 3D] FIG. 1 shows SEM images of the film surface of stretched PP C7054-07NA film after 25% cold stretch at 100 mm / sec (room temperature) and 50% hot stretch at 5 mm / sec (100° C.), indicated by the 10 micron scale bar. [Figure 4A] FIG. 1 shows a TEM image of PP C7054-07NA film before stretching, indicated by the 1 micron scale bar. [Figure 4B] FIG. 1 shows TEM images of PP C7054-07NA film after 25% cold stretch at 100 mm / sec (room temperature) and 100% hot stretch at 5 mm / sec (100° C.), with 1 micron scale bar indicated. [Figure 4C] FIG. 1 shows a TEM image of PP INSPIRE® 114 film before stretching, indicated by the 0.2 micron scale bar. [Figure 4D] FIG. 1 shows a TEM image of PP INSPIRE® 114 film after 25% cold stretch at 100 mm / sec (room temperature) and 100% hot stretch at 5 mm / sec (100° C.), with the 0.2 micron scale bar indicated. [Figure 5A] 1 shows wide angle X-ray scattering (WAXS) data of PP C7054-07NA film before stretching. [Figure 5B] 1 shows wide angle X-ray scattering (WAXS) data of PP C7054-07NA microporous film after 25% cold stretching at 100 mm / sec (room temperature) followed by 100% hot stretching at 5 mm / sec (100° C.). [Figure 5C] 1 shows wide angle X-ray scattering (WAXS) data of PP TI4020N film before stretching. [Figure 5D] 1 shows wide angle X-ray scattering (WAXS) data of PP TI4020N microporous film after 25% cold stretching at 100 mm / sec (room temperature) followed by 100% hot stretching at 5 mm / sec (100° C.). [Figure 6A] FIG. 1 shows a TEM image of a film from a 20 / 80 blend of homopolymers PP H314 (20%) and PP C7054-07NA (80%) before stretching, indicated by the 1 micron scale bar. [Figure 6B] FIG. 1 shows a TEM image of a film from a 20 / 80 blend of homopolymer PP H314 (20%) and PP C7054-07NA (80%) after 25% cold stretching at 100 mm / sec (room temperature) and 100% hot stretching at 5 mm / sec (100° C.), with the 0.5 micron scale bar indicated. [Figure 7A] 1 shows mercury intrusion porosimetry data for a 762 μm (30 mil) thick film of PP C7054-07NA after 25% cold stretching at 100 mm / sec (room temperature) and 100% hot stretching at 5 mm / sec (100° C.). [Figure 7B] 1 shows mercury intrusion porosimetry data for a 762 μm (30 mil) thick film of PP C7054-07NA after a 25% cold stretch (room temperature) at 100 mm / sec, followed by a 150% hot stretch (100° C.) at 5 mm / sec. [Figure 8] One suitable multi-stage drawing process for either cold or hot machine direction orientation (MDO) of films using rolls is shown. [Figure 9] One suitable multi-stage stretching process for transverse direction orientation (TDO) of a film using an oven is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention can be more readily understood by reference to the following detailed description, examples, drawings and claims, as well as their preceding and following descriptions. However, it should be understood that the present invention is not limited to the specific compositions, articles, devices, systems and / or methods disclosed, unless otherwise specified, and as such may, of course, vary. Although aspects of the present invention may be described and claimed in certain legal classifications, such as composition legal classifications, this is for convenience only, and one of ordinary skill in the art will understand that each aspect of the present invention may be described and claimed in any legal classification.

[0016] The following detailed description of the invention is also provided as an enabling teaching of the best currently known embodiment of the invention. To this end, those skilled in the art will recognize and understand that modifications and variations to the various aspects of the invention described herein may be made while still obtaining the beneficial results of the invention. It will also be understood that some of the benefits of the invention can be obtained by selecting some of the features of the invention without using other features. Thus, those skilled in the art will recognize that many modifications and adaptations to the invention are possible and that such many modifications and adaptations may even be desirable in some circumstances and therefore are also part of the invention.

[0017] While the present invention can be embodied in various forms, the following description of some embodiments is made with the understanding that the present disclosure is to be considered as an example of the present invention and is not intended to limit the present invention to the specific embodiments illustrated. Headings are provided for convenience only and should not be construed as limiting the present invention in any way. An embodiment illustrated in any heading or in any portion of this disclosure may be combined with an embodiment illustrated in the same or any other heading or portion of this disclosure.

[0018] Any combination of the elements described herein in all possible variations thereof is encompassed by the invention unless otherwise indicated herein or otherwise clearly contradicted by context.

[0019] Unless expressly stated otherwise, any method or aspect described herein is never intended to be construed as requiring that its steps be performed in a particular order. Thus, unless a method claim specifically recites in the claims or description that the steps are limited to a particular order, no order is intended to be inferred in any sense. This applies to all possible non-expressive bases for interpretation, including logical matters regarding the arrangement or operational flow of steps, simple meaning derived from grammatical constructions or punctuation, or the number or type of embodiments described herein. It should be understood that both the foregoing summary and the following detailed description are exemplary and explanatory only, and not restrictive.

[0020] All publications mentioned herein are incorporated herein by reference to disclose and describe the methods and / or materials in connection with which the publications are cited.

[0021] It should be understood that the terminology used herein is merely for the purpose of describing certain aspects and is not intended to be limiting. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. In this specification and in the claims that follow, reference will be made to a number of terms defined herein.

[0022] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0023] As used herein, the term "and / or" means "and or alternatively."

[0024] As used herein, the term "optional" or "optionally" means that the described event, condition, ingredient, or circumstance may or may not occur, and that the description includes instances in which said event, condition, ingredient, or circumstance occurs and instances in which said event, condition, ingredient, or circumstance does not occur.

[0025] As used herein, any disclosure using the term "comprises" or "comprising" includes similar disclosures, where "comprises" or "comprising" is instead replaced by "consisting of" or "consisting of," or instead replaced by "consisting essentially of" or "consisting essentially of."

[0026] As used herein, the phrase "sufficient" (e.g., "conditions sufficient to") refers to a value or condition sufficient to perform a function or property for which such value or condition is expressed. As noted below, the exact values ​​or specific conditions required may vary from embodiment to embodiment depending on recognized variables such as the materials and / or processing conditions used.

[0027] The term "by weight", when used in conjunction with a component, is based on the total weight of the formulation or composition in which the component is included, unless otherwise specified. For example, when a particular element or component in a composition or article is said to be present in an amount of 8% by weight (also written as 8 wt.%), it is understood that this percentage is relative to the overall composition percentage of 100%. The weight % of component A in a composition is the weight of component A expressed as a percentage of the total weight of the composition, and is conventionally described as "weight % of A based on the total weight of the composition". In some examples, the weight percentage of a component is based on the total weight of the composition on a "dry basis", which refers to the weight of the composition without water (e.g., less than about 1% by weight, less than about 0.5% by weight, less than about 0.1% by weight, less than about 0.05% by weight, or about 0% by weight water based on the total weight of the composition).

[0028] In the present specification, when a numerical value is disclosed, such as 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, etc., the following sentence typically follows such numerical value: "The foregoing numerical values ​​can be used with the terms "about", "at least about", or "less than about", respectively, and any of the foregoing numerical values ​​can be used alone to describe an open-ended range, or in combination with a limiting range description." This sentence means that each of the foregoing numerical values ​​can be used alone (e.g., 4), can be preceded by the word "about" (e.g., about 8), can be preceded by the phrase "at least about" (e.g., at least about 2), can be preceded by the phrase "less than about" (e.g., less than about 7), or can be used in any combination with or without any of the preceding words or phrases to define a range (e.g., 2 to 9, about 1 to 4, 8 to about 9, about 1 to about 10, etc.). Furthermore, when a range is described as "less than about X", this phrase is instead equivalent to the range that is the combination of "about X" and "less than about X". For example, "about 10 or less" is the same as "about 10 or less than about 10." Such interchangeable range descriptions are contemplated herein. Other range formats are disclosed herein, but the difference in format should not be construed to imply a difference in substance.

[0029] As used herein, "continuous" refers to a process whose duration is continuous or which is interrupted, halted or stopped only momentarily compared to the duration of the process. A process is "continuous" when starting materials or reactants are supplied to an apparatus without interruption or substantially without interruption, or when the processing of said starting materials or reactants is not carried out in a batch process.

[0030] As used herein, the term "substantially free" means a composition having less than about 1% by weight, e.g., less than about 0.5% by weight, less than about 0.1% by weight, less than about 0.05% by weight, or less than about 0.01% by weight of the indicated substance, based on the total weight of the composition.

[0031] As used herein, the term "substantially" when used in reference to a composition means at least about 60% by weight, e.g., at least about 65% by weight, at least about 70% by weight, at least about 75% by weight, at least about 80% by weight, at least about 85% by weight, at least about 90% by weight, at least about 91% by weight, at least about 92% by weight, at least about 93% by weight, at least about 94% by weight, at least about 95% by weight, at least about 96% by weight, at least about 97% by weight, at least about 98% by weight, at least about 99% by weight, or about 100% by weight of a particular feature or component, based on the total weight of the composition.

[0032] All molecular weights and other values ​​related to molecular weight (such as polydispersity index) disclosed herein are determined by gel permeation chromatography (GPC).

[0033] As used herein, the terms “molar mass distribution”, “MMD” and “molecular weight distribution” are used interchangeably and refer to the number of moles of each polymer species or the number of polymer chains (N i ) and the molar mass (M i ) or describes the relationship between polymer chains. The molar mass distribution of a polymer may vary depending on the polymer fraction. Depending on the statistical method applied, different average values ​​may be defined and are described herein.

[0034] As used herein, the term "number average molecular weight" (M n or

number

number

[0035] As used herein, the term "weight average molecular weight" (M w or

number

number

[0036] As used herein, gel permeation chromatography (GPC) refers to a chromatographic separation method in which molecules in a solution are separated by their size. Separation is achieved by differential rejection of sample molecules as they pass through a bed of porous particles known as a separation column. GPC can be used to determine a substantially accurate molar mass distribution of polymer molecules. For example, a constant volume of the liquid fraction (eluent) that passes through the column is collected. As the polymer elutes through the column, molecules that are too large to pass through the pores of the column are rejected from the packed pore volume and elute at an earlier retention time, while smaller molecules enter the pores of the column and elute at a later time. The concentration of the eluted polymer can be measured by spectroscopic techniques, such as, for example, refractive index (RI) and ultraviolet (UV). The eluent stream can also be continuously analyzed by RI, low angle laser light scattering (LALLS), multi-angle laser scattering (MALLS), UV and / or viscosity measurements.

[0037] The use of numerical values ​​in the various quantitative values ​​set forth in this application is described as approximations, unless expressly indicated otherwise, as if the minimum and maximum values ​​in the stated ranges were both preceded by the word "about". In this manner, slight variations from the stated values ​​may be used to achieve substantially the same results as the stated values. The disclosure of ranges also contemplates a continuous range, including all values ​​between the minimum and maximum values ​​recited, and any ranges that may be formed by such values. Also disclosed herein are any and all ratios (as well as any such ratio ranges) that may be formed by dividing a recited numerical value into any other recited numerical value. Thus, one skilled in the art will appreciate that many such ratio, range and ratio ranges may be explicitly derived from the numerical values ​​presented herein, and in all instances, such ratio, range and ratio ranges represent various embodiments of the present invention.

[0038] As used herein, "average pore size" refers to the "average pore diameter" measured by mercury intrusion porosimetry (4V / A by UOP method 578-11 described below) as known to those skilled in the art or known in the field of mercury intrusion porosimetry. The UOP method is available from ASTM International, West Conshohocken, PA, USA (or via www.astm.org). Since the average is the median average, the term may be described herein as "median pore diameter."

[0039] As used herein, the term "polypropylene copolymer" refers to a copolymer that includes a polymeric backbone, side chains, or chain segments of polypropylene, and in particular, such backbone, side chains, or chain segments include 15 or more consecutive polymerized units of propylene. As disclosed herein, preferred PP copolymers include polypropylene homopolymer chain segments (e.g., isotactic PP) and ethylene-containing copolymer chain segments. In some embodiments, the ethylene-containing copolymer chain segments are ethylene-propylene (EP) copolymer chain segments, and such polypropylene copolymers may also be described herein as PP-EP copolymers.

[0040] In some embodiments, the present invention relates to a microporous polymeric film comprising one or more polypropylene copolymers (PP copolymers), which may comprise one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments.

[0041] In some embodiments, the PP copolymer comprises a polypropylene homopolymer chain segment in an amount of at least about 50% by weight based on the total weight of the PP copolymer, and the maximum amount of the polypropylene homopolymer chain segment is not particularly limited. In the same or other embodiments, the PP copolymer comprises a polypropylene homopolymer chain segment in an amount of up to about 95% by weight based on the total weight of the PP copolymer, and the minimum amount of the polypropylene homopolymer chain segment is not particularly limited. For example, the PP copolymer may comprise a polypropylene homopolymer chain segment in an amount of 44, 46, 48, 50, 52, 54, 56, 58, 60, 62, 64, 65, 66, 68, 70, 72, 74, 76, 78, 80, 82, 84, 86, 88, 90, 95% (in weight % based on the weight of the PP copolymer). Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open-ended range or in combination to describe a limited range. For example, but not limited to, the amount of polypropylene homopolymer chain segments in the PP copolymer can be at least about 50% by weight, about 50% to about 82% by weight, or about 60% to about 82% by weight, based on the total weight of the PP copolymer. In terms of mole percent, the PP copolymer can include polypropylene homopolymer chain segments in an amount of 40, 42, 43, 44, 45, 46, 47, 48, 49, 50, 52, 54, 55, 56, 58, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 79, 80, 82, or 85% (in mole percent based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the PP copolymer). Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe open-ended ranges, or in combination to describe limiting ranges.For example, but not limited to, the amount of polypropylene homopolymer chain segments in the PP copolymer can be at least about 43 mol %, about 43 mol % to about 79 mol %, or about 50 mol % to about 79 mol %, based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the PP copolymer.

[0042] In some embodiments, the PP copolymer comprises at least about 5% by weight of ethylene-containing copolymer chain segments based on the total weight of the PP copolymer, and the maximum amount of ethylene-containing copolymer chain segments is not particularly limited. In the same or other embodiments, the PP copolymer comprises up to about 50% by weight of ethylene-containing copolymer chain segments based on the total weight of the PP copolymer, and the minimum amount of ethylene-containing copolymer chain segments is not particularly limited. For example, the PP copolymer may comprise 5, 10, 15, 17, 18, 19, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54 or 55% (in weight % based on the weight of the PP copolymer) of ethylene-containing copolymer chain segments. Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open-ended range, or in combination to describe a limited range. For example, without limitation, the amount of ethylene-containing copolymer chain segments in the PP copolymer may be at least about 10 wt%, about 18 wt% to about 50 wt%, or about 25 wt% to about 40 wt%, by weight based on the total weight of the PP copolymer. Preferably, the ethylene-containing copolymer chain segments in the PP copolymer are ethylene-propylene (EP) copolymer chain segments. In terms of mole %, the PP copolymer may contain ethylene-containing copolymer chain segments in an amount of 10, 15, 17, 18, 19, 20, 21, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 55%, 57 or 60% (in mole % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the PP copolymer). Each of the foregoing numbers may be preceded by the word "about", "at least about" or "less than about", and any of the foregoing numbers may be used alone to describe an open range or in combination to describe a limited range.For example, but not limited to, the amount of ethylene-containing copolymer chain segments in the PP copolymer can be at least about 15 mol%, about 21 mol% to about 57 mol%, or about 21 mol% to about 45 mol%, based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the PP copolymer.

[0043] In some embodiments, the ethylene-containing copolymer chain segment in the PP copolymer comprises at least 45% by weight of polymerized units of ethylene based on the total weight of the ethylene-containing copolymer chain segment, and the maximum amount of ethylene in the ethylene-containing copolymer chain segment is not particularly limited. For example, the ethylene unit content in the ethylene-containing copolymer chain segment in the PP copolymer can be 40, 42, 44, 45, 46, 47, 48, 49, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68, 70, 72, 75 or 80% (in weight % based on the weight of the ethylene-containing copolymer chain segment). Each of the above numbers can be preceded by the word "about", "at least about" or "less than about", and any of the above numbers can be used alone to describe an open range or in combination to describe a limited range. For example, but not limited to, the amount of ethylene units in the ethylene-containing copolymer chain segment in the PP copolymer can be at least about 45% by weight, about 45% to about 80% by weight, or about 45% to about 60% by weight based on the total weight of the ethylene-containing copolymer chain segment. In terms of mole %, the ethylene unit content in the ethylene-containing copolymer chain segment in the PP copolymer can be an amount of 50, 52, 54, 55, 56, 57, 58, 59, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 80, 82, 85, or 90% (in mole % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment). Each of the foregoing numbers can be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers can be used alone to describe an open-ended range or in combination to describe a limited range. For example, but not limited to, the amount of ethylene units in the ethylene-containing copolymer chain segment in the PP copolymer can be at least about 55 mol %, about 55 mol % to about 80 mol %, or about 55 mol % to about 69 mol %, based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment.Preferably, the ethylene-containing copolymer chain segment in the PP copolymer is an ethylene-propylene (EP) copolymer chain segment, in which case the above percentages refer to the % ethylene unit content (either by weight or by mole, as described above) in the EP copolymer chain segment.

[0044] The total ethylene content in polymerized form in the PP copolymer is at least 10 wt. %, such as from 10 to 30 wt. % or even from 15 to 25 wt. %, based on the weight of the PP copolymer, or at least 14 mol. %, such as from 14 to 39 mol. % or from 15 to 25 mol. %, based on the molar content of polymerized units of ethylene in the PP copolymer, as a percentage of the total molar content of polymerized monomer units in the PP copolymer.

[0045] The microporous polymer film may essentially consist of one or more polypropylene copolymers (PP copolymers) comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments.Thus, in at least some embodiments, the same amounts and ranges outlined above for the polypropylene homopolymer chain segments and ethylene-containing copolymer chain segments in the PP copolymer are also appropriate for the amounts and ranges of the polypropylene homopolymer chain segments and ethylene-containing copolymer chain segments in the microporous polymer film.

[0046] In some embodiments, the microporous polymer film comprises a polypropylene homopolymer chain segment in an amount of at least about 50% by weight based on the total weight of the microporous polymer film, and the maximum amount of the polypropylene homopolymer chain segment is not particularly limited. In the same or other embodiments, the microporous polymer film comprises a polypropylene homopolymer chain segment in an amount of up to about 95% by weight based on the total weight of the microporous polymer film, and the minimum amount of the polypropylene homopolymer chain segment is not particularly limited. For example, the microporous polymer film may comprise a polypropylene homopolymer chain segment in an amount of 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 95% (in weight % based on the weight of the microporous polymer film). Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open range, or in combination to describe a limited range. For example, without limitation, the amount of polypropylene homopolymer chain segments in the microporous polymer film may be at least about 50% by weight, about 50% by weight to about 82% by weight, or about 60% by weight to about 82% by weight, based on the total weight of the microporous polymer film. In terms of mole percent, the microporous polymer film may contain a polypropylene homopolymer chain segment in an amount of 40, 42, 43, 44, 45, 46, 47, 48, 49, 50, 52, 54, 55, 56, 58, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 79, 80, 82, or 85% (in mole percent based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segment as a percentage of the total molar content of polymerized monomer units in the microporous polymer film). Each of the foregoing numbers may be preceded by the words "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open-ended range or in combination to describe a limited range.For example, but not limited to, the amount of polypropylene homopolymer chain segments in the microporous polymer film can be at least about 43 mol%, about 43 mol% to about 79 mol%, or about 50 mol% to about 80 mol% based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0047] The polypropylene homopolymer chain segments present in the microporous polymer film may be derived solely from the PP copolymer component, or may be a combination of polypropylene homopolymer chain segments derived from the PP copolymer component and one or more other polymer components (PP homopolymers or other copolymers containing polypropylene homopolymer chain segments) that contain polypropylene homopolymer chain segments. Preferably, the polypropylene homopolymer chain segments present in the microporous polymer film are derived solely from the PP copolymer component.

[0048] In some embodiments, the microporous polymer film comprises at least about 5% by weight of ethylene-containing copolymer chain segment based on the total weight of the microporous polymer film, and the maximum amount of ethylene-containing copolymer chain segment is not particularly limited.In the same or other embodiments, the microporous polymer film comprises up to about 60% by weight of ethylene-containing copolymer chain segment based on the total weight of the microporous polymer film, and the minimum amount of ethylene-containing copolymer chain segment is not particularly limited.For example, the microporous polymer film can comprise 5, 10, 15, 17, 18, 19, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 55, 56, 58 or 60% (based on the weight of the microporous polymer film). Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open-ended range, or in combination to describe a limited range. For example, without limitation, the amount of ethylene-containing copolymer chain segments in the microporous polymer film may be at least about 10 wt%, about 18 wt% to about 50 wt%, or about 25 wt% to about 40 wt%, based on the total weight of the microporous polymer film. In terms of mole percent, the microporous polymer film may contain 10, 15, 17, 18, 19, 20, 21, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, 52, 54, 55, 57, or 60% of the ethylene-containing copolymer chain segment (based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the microporous polymer film). Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open-ended range or in combination to describe a limited range.For example, but not limited to, the amount of ethylene-containing copolymer chain segments in the microporous polymer film can be at least about 15 mol%, about 21 mol% to about 57 mol%, or about 20 mol% to about 45 mol%, based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0049] The ethylene-containing copolymer chain segment present in the microporous polymer film may be derived only from the PP copolymer component, or may be a combination of ethylene-containing copolymer chain segments derived from the PP copolymer component and one or more other polymer components (e.g., EP copolymers) that contain ethylene-containing copolymer chain segments.Preferably, the ethylene-containing copolymer chain segment present in the microporous polymer film is derived only from the PP copolymer component.Preferably, the ethylene-containing copolymer chain segment is an ethylene-propylene (EP) copolymer chain segment.

[0050] In some embodiments, the ethylene-containing copolymer chain segment in the microporous polymer film comprises at least 45% by weight of ethylene polymerized units based on the total weight of the ethylene-containing copolymer chain segment, and the maximum amount of ethylene in the ethylene-containing copolymer chain segment is not particularly limited.For example, the ethylene unit content in the ethylene-containing copolymer chain segment in the microporous polymer film can be 40, 42, 44, 45, 46, 47, 48, 49, 50, 52, 54, 56, 58, 60, 62, 64, 66, 68, 70, 72, 75 or 80% (based on the weight of the ethylene-containing copolymer chain segment in weight %).Each of the above numbers can be preceded by the words "about", "at least about" or "about to less than", and any of the above numbers can be used alone to describe an open range or in combination to describe a limited range. For example, but not limited to, the amount of ethylene units in the ethylene-containing copolymer chain segment in the microporous polymer film can be at least about 45% by weight, about 45% to about 80% by weight, or about 45% to about 60% by weight based on the total weight of the ethylene-containing copolymer chain segment. In terms of mole %, the ethylene unit content in the ethylene-containing copolymer chain segment in the microporous polymer film can be in an amount of 50, 52, 54, 55, 56, 57, 58, 59, 60, 62, 64, 66, 68, 70, 72, 74, 76, 78, 80, 82, 85, or 90% (in mole % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment). Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe open-ended ranges, or in combination to describe limiting ranges.For example, but not limited to, the amount of ethylene units in the ethylene-containing copolymer chain segment in the microporous polymer film can be at least about 55 mol%, about 55 mol% to about 80 mol%, or about 55 mol% to about 69 mol% based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment.Preferably, the ethylene-containing copolymer chain segment in the PP copolymer is an ethylene-propylene (EP) copolymer chain segment, in which case the above percentages refer to the ethylene unit content % (either weight % or mole % as described above) in the EP copolymer chain segment.

[0051] The total ethylene content in polymerized form in the microporous polymer film is at least 10 wt.%, such as from 10 to 30 wt.%, or even from 15 to 25 wt.%, based on the weight of the microporous polymer film, or at least 14 mol.%, such as from 14 to 39 mol.%, or from 15 to 25 mol.%, or from 21 to 33 mol.%, based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0052] In certain embodiments, these PP copolymers can be produced in a reactor from one or more components of PP homopolymers and one or more components of ethylene-containing copolymers. Preferably, the ethylene-containing copolymer is an ethylene-propylene (EP) copolymer. Thus, the present invention provides a microporous polymer film comprising a polypropylene copolymer produced from the reaction product of a polypropylene homopolymer and an ethylene-propylene copolymer.

[0053] In certain embodiments where the ethylene-containing copolymer is an ethylene-propylene (EP) copolymer, the microporous film may consist essentially of a PP-EP copolymer comprising one or more polypropylene homopolymer chain segments and one or more ethylene-propylene copolymer chain segments. In certain such embodiments, the weight ratio of the PP component to the EP component may be 50:50, 55:45, 60:40, 65:35, 67:33, 70:30, 72:28, 74:26, 76:24, 78:22, 79:21, 80:20, 81:19, 82:18, 84:16, 86:14, 88:12, 90:10, or 95:5. Each of the foregoing numbers may be preceded by the words "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open-ended range or in combination to describe a limited range. For example, the weight ratio can be at least about 60:40, from about 65:35 to about 85:15, or less than about 90:10.

[0054] The ethylene-containing copolymers can be random, alternating or block copolymers, and the ethylene-propylene copolymers can be random EP copolymers, alternating EP copolymers or EP block copolymers. For example, a PP copolymer comprising an EP copolymer backbone or chain segment can comprise a random EP copolymer backbone or chain segment, an alternating EP copolymer backbone or chain segment or a diblock copolymer backbone or chain segment. For example, a diblock copolymer can comprise a polypropylene block and a polyethylene block, or a polypropylene block and an EP copolymer block, or a polyethylene block and an EP copolymer block. Other ethylene-containing copolymers can also be used.

[0055] The film can be made from the PP copolymer or its polymer blend by any method known in the art, most conveniently by heating to a temperature sufficient to obtain the PP copolymer (or its blend) in molten form, followed by extrusion or blown film extrusion. In some embodiments, the film can be a multilayer film. The multilayer film can be coextruded, whereby a first layer is coextruded with a second layer.

[0056] Prior to stretching, the non-porous polymer film may have a morphology characterized by a majority polypropylene phase (or matrix) in the polymer film, minor polymer regions of ethylene-containing copolymers such as ethylene-propylene copolymer regions, and inclusion of a major polypropylene phase in the minor polymer regions. This allows for efficient transfer of stretching forces from the major phase to the minor regions, splitting the minor regions and then initiating and developing micropores upon stretching. Thus, the non-porous films disclosed herein may be subjected to a stretching process (described herein) to produce microporous films.

[0057] In one embodiment, the microporous film described herein is oriented in the machine direction. The microporous film may be oriented by cold stretching in the machine direction and hot stretching in the machine direction after cold stretching. Alternatively or in addition, either one or more cold stretches and / or one or more hot stretches may be performed in any other direction, such as, for example, the transverse direction (across the machine direction). The cold stretch percentage may be 25% to 150%, and is represented by Formula I:

number

[0058] Cold stretching can be carried out at temperatures ranging from 10° C. to 50° C., but is typically carried out at room temperature. Unless specified to the contrary, cold stretching is carried out at room temperature. As used herein, "room temperature" is considered to be a temperature of 15° C. to 25° C. (and more typically 20 to 23° C.). The hot stretch percentage can be from 50% to 500% and is represented by Formula II:

number

[0059] The hot stretching may be carried out at a temperature ranging from 90°C to 140°C.

[0060] In some embodiments, a method of making a microporous film includes providing a microporous film as described herein and cold stretching the film in the machine direction at a temperature ranging from -20°C to 50°C, preferably 10°C to 50°C, to a cold stretch percentage of 25% to 200%. The cold stretch percentage is determined using formula I above. After cold stretching, the film is subjected to hot stretching in the machine direction at a temperature ranging from 50°C to 150°C, preferably 90°C to 140°C or 100°C to 140°C, to a hot stretch ratio of 50% to 500%. The hot stretch percentage is determined using formula II above.

[0061] In one embodiment, the stretching process optionally comprises one or more Heat Set The process includes one or more cold stretching steps followed by one or more hot stretching steps with a stretch step. The process may optionally include a post-annealing step. Film uniformity is important, so it is preferred to keep the temperature below 150°C.

[0062] In one embodiment, the stretching process may be performed as the film travels along a manufacturing line that may include a series of rollers. The degree of stretching in the machine direction may be controlled by using different speed rollers or by different diameters of the rollers. Optionally, the degree of stretching in the transverse direction may be performed, which may be controlled by gripping the ends of the web and stretching the film in the transverse (cross) direction between a series of clips that traverse down a pair of adjustable diverging rails. The polymer film at the front end of the manufacturing line may appear clear and colorless (before stretching), but as it travels along the manufacturing line, such as along the area where the stretching process is performed, it may appear to change to an increasing opacity, a white haze develops, and then the film turns white due to the formation of pores (and the associated light scattering effects from the void spaces).

[0063] Processes for stretching nonporous films to produce microporous films have been previously reported (see, for example, U.S. Pat. No. 3,801,404 to Druin et al. and U.S. Pat. No. 3,426,754 to Bierenbaum et al.), however, these reported processes using polyethylene or polypropylene films involve stretching the films prior to the stretching process (or at intermediate points between separate film stretching stages), and sometimes at separate stretching steps after the stretching process. Heat Set With steps annealing However, annealing The extended time period is problematic in view of the desired objective of running a continuous manufacturing line for producing microporous films. Ideally, annealing A continuous extrusion and pore forming process in one continuous production line without the need for a holding period for extended steps is preferred. Advantageously, films made from the PP copolymers (and blends thereof) described herein can be made without any additional steps to produce microporous films from the stretching process. annealing Step or Heat Set(In this case, the mechanism of pore formation is different from that of previously reported polyethylene and polypropylene films.) Thus, the PP copolymers described herein can be heated and extruded to form non-porous films that can be stretched in a continuous manufacturing line to produce microporous films.

[0064] In certain embodiments, the invention described herein provides a microporous polymer film comprising one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the polypropylene homopolymer chain segments being in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film, and (ii) ethylene-containing copolymer chain segments being in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film, and (iii) ethylene-containing copolymer chain segments being in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. and ethylene-containing copolymer chain segments in a total amount of 18 to 50 wt % based on the weight of the film or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segments, wherein at least a portion of the ethylene-containing copolymer chain segments contain polymerized units of ethylene in an amount of at least 45 wt % based on the weight of the ethylene-containing copolymer chain segments or at least 55 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segments.

[0065] In one embodiment, a method of forming a microporous polymeric film, the method steps include: (a) dissolving one or more polypropylene copolymers, comprising: (i) one or more polypropylene homopolymer chain segments in a total amount of from 50 to 82 wt % based on the weight of the polypropylene copolymer or from 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer; and (ii) one or more ethylene-containing copolymer chain segments in a total amount of from 18 to 50 wt % based on the weight of the polypropylene copolymer or from 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer. and the ethylene-containing copolymer chain segment above, wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of at least 45 wt %, based on the weight of the ethylene-containing copolymer chain segment, or at least 55 mol %, based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment, as a percentage of the total molar content of polymerized monomer units of the ethylene-containing copolymer chain segment; (b) forming a non-porous film from the polypropylene copolymer; and (c) subjecting the non-porous film to successive cold and hot stretching steps, including (i) at least one cold stretching step at a temperature in the range of -20°C to 50°C, and (ii) at least one hot stretching step at a temperature in the range of 50°C to 150°C, thereby producing a microporous polymer film.

[0066] In some embodiments, the method is a continuous process for producing a microporous polymeric film. In particular, in some embodiments, the method does not include any additional steps after the formation of a non-porous film. annealing The process proceeds without any steps, and any subsequent steps after the formation of the microporous polymer film. annealing or Heat SetIt proceeds without any steps and is a continuous process for producing microporous polymer films.

[0067] The present invention relates to the microporous films produced by the methods described herein, and further relates to articles produced from the microporous films described herein.

[0068] The total thickness of the microporous film is not particularly limited and may be less than 100 mils in some embodiments. Different end uses may require different film thicknesses, or conversely, different film thicknesses may be more appropriate for some end uses. For example, a microporous film suitable for use as a house wrap may have a thickness of 2 to 10 mils, preferably 4 to 7 mils. A microporous film suitable for use as a roof membrane in Europe may have a thickness of 4 to 20 mils, preferably 5 to 10 mils, or a microporous film suitable for use as a roof membrane in North America may have a thickness of 20 to 80 mils, preferably 40 to 60 mils. Also, microporous films suitable for medical applications such as packaging wraps for surgical packs may have a thickness in the range of 51 to 508 μm (2 to 20 mils), for example 127 to 254 μm (5 to 10 mils) thick.

[0069] The thickness of the film may depend on the end use of the microporous film discussed herein, and all thicknesses and thickness ranges are considered suitable for the microporous film of the present invention. Accordingly, all individual values ​​and subranges less than 2540 μm (100 mils) are included and disclosed herein. For example, in some embodiments, the total thickness of the microporous film (in μm) may be 2540, 2032, 1524, 1270, 1016, 762, 508, 381, 254, 203, 178, 152, 127, 102, 51, 38, 25, 13 or 2.5 μm. Each of the above numbers may be preceded by the words "about," "at least about," or "less than about," and any of the above numbers may be used alone to describe an open range or in combination to describe a limited range. In further embodiments, the total thickness of the microporous film can be from 0.1 to 6 mils, from 0.1 to 4 mils, from 0.1 to 2 mils, or from 0.1 to 2 mils. In further embodiments, the total thickness of the film can be from 0.1 to 1.5 mils.

[0070] The films described herein are microporous with specific pore sizes and porosities that can be altered to control the desired and useful barrier properties for a selected end use. For house wrap films and roof membranes, the same types of barrier properties are important, such as water vapor transmission rate (WVTR) and permeation. Water vapor transmission rate is dependent on film thickness. Permeation is essentially the normalized water vapor transmission rate (assuming a constant pressure difference across the film when comparing different film samples), and WVTR is recorded adjusted for film thickness, and all "perms" herein are US perms. 1 US perm = 5.72 x 10 -8 g / Pa·s·m 2 For architectural wrap applications, a suitable average pore diameter (nm) may be 30-300 nm, and a suitable film porosity may be 25-55% to achieve a water vapor transmission rate of 10-100 perms (and a WVTR of 70-700 g / 24 h m). 2Also, for roof membranes, a suitable median average pore diameter (nm) may be 30-250 nm, and a suitable film porosity to achieve a permeability of 10-70 perms may be 25-45% (and a WVTR of 70-500 g / 24 h m). 2 In the medical packaging field, the same barrier properties are important, but the focus on permeability is usually on air (or gas sterilant) permeability measured as Gurley air permeability and maximum penetration (calculated %P) in the ASTM F2638 test (for porous packaging as a surrogate microbial barrier). max For medical packaging, the appropriate mean pore diameter (nm) may be between 300 and 1,000 nm, and the barrier to bacteria / microorganisms is between 1 and 100 s / 100 cm. 3 Useful range of Gurley air permeability and calculated %P below 10 max The appropriate film porosity to achieve this value may be 55-75% (P max (For , the smaller the better).

[0071] In some embodiments, the microporous polymer film has a porosity of at least about 20%, and the maximum porosity is not particularly limited. In the same or other embodiments, the microporous polymer film has a porosity of up to about 75%, and the minimum porosity is not particularly limited. For example, the microporous polymer film may have a porosity (%) of 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80%. Each of the foregoing numbers may be preceded by the words "about", "at least about" or "less than about", and any of the foregoing numbers may be used alone to describe an open range or in combination to describe a limited range. For example, but not limited to, the microporous polymer film may have a porosity of at least about 20%, about 20% to about 75%, or about 25% to about 70%.

[0072] In some embodiments, the microporous polymer film has a median average pore diameter (by volume) of at least about 20 nm, and the maximum median pore diameter is not particularly limited. In the same or other embodiments, the microporous polymer film has a median pore diameter of up to about 2000 nm, and the minimum median pore diameter is not particularly limited. For example, the microporous polymer film can have a median pore diameter (nm) of 10, 15, 20, 25, 30, 40, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900, 1000, 1500, 2000 nm. Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe open-ended ranges or in combination to describe limited ranges. For example, but not limited to, the microporous polymer film may have a median pore diameter of at least about 20 nm, from about 20 nm to about 1000 nm, or from about 25 nm to about 1000 nm.

[0073] In some embodiments, the microporous polymer film has a permeability of at least about 1 perm, and the maximum permeability is not particularly limited. In the same or other embodiments, the microporous polymer film has a permeability of up to about 150 perms, and the minimum permeability is not particularly limited. For example, the microporous polymer film may have a permeability (perm) of 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, or 150 perms. Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe an open-ended range, or in combination to describe a limited range. For example, without limitation, the microporous polymer film can have a transmission of at least about 10 perms, from about 10 perms to about 100 perms, or from about 20 perms to about 100 perms.

[0074] In some embodiments, the microporous polymer film has a microporous viscosity of at least about 1 s / 100 cm3 In the same or other embodiments, the microporous polymer film has a Gurley Hill Porosity (herein referred to as "Gurley Air Permeability") of about 35,000 s / 100 cm and the maximum Gurley Air Permeability is not particularly limited. 3 For example, the microporous polymer film may have a Gurley air permeability of up to 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140 or 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1500, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 15000, 20000, 25000, 30000, 35000 s / 100 cm 3 Gurley breathability (s / 100cm 3 Each of the foregoing numbers may be preceded by the words "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe open ranges or in combination to describe limited ranges. For example, but not limited to, a microporous polymeric film may have a microporous density of at least about 1 s / 100 cm 3 , about 1s / 100cm 3 ~About 10000s / 100cm 3 , or about 10s / 100cm 3 ~About 5000s / 100cm 3 , or about 10s / 100cm 3 ~About 1000s / 100cm 3 , or about 10s / 100cm 3 ~About 100s / 100cm 3 It may have a Gurley breathability of 100%.

[0075] In some embodiments, the microporous polymer film has a % Maximum Penetration (%P) calculated by ASTM F2638-18 test of less than about 10. max ) and has a barrier against microorganisms, as measured by maxis not particularly limited. For example, the microporous polymer film has a calculated %P of less than 10, 5, 2, 1, 0.5, 0.2, 0.1, 0.05, 0.03, 0.02, 0.015, 0.010, or 0.005. max Each of the foregoing numbers may be preceded by the word "about," "at least about," or "less than about," and any of the foregoing numbers may be used alone to describe open ranges or in combination to describe limited ranges. For example, but not limited to, a microporous polymeric film may have a calculated %P of less than about 10, about 0 to about 10, or about 0 to about 1. max Ideally, the calculated %P max The value is zero, but the limit for detection cannot be zero. Calculated %P max can be from about 0.005 or less to about 10, or from about 0.005 or less to about 5, or from about 0.005 or less to about 1.

[0076] The films described herein do not use the addition of fillers such as calcium carbonate, CaCO3, etc. to produce a water vapor breathable film with high water vapor transmission. Thus, the films described herein contain less than 5 wt% of fillers based on the total weight of the polymers present in the film. Exemplary fillers may include, but are not limited to, CaCO3, clay, silica, alumina, titania, zirconia, ceria, talc, magnesium carbonate, calcium sulfate, barium sulfate, porous glass beads, porous polymer beads, ceramic beads, aluminum trihydroxide, magnesium trihydroxide, wollastonite whiskers, wood flour, lignin, starch, clay, carbon black, graphite, graphene, carbon nanotubes, carbon fibers, carbon nanofibers, or combinations thereof. In further embodiments, the films described herein contain less than 3 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt% of fillers based on the total weight of the polymers present in the film. In some embodiments, the films described herein contain no fillers (0 wt%). In many pharmaceutical applications, 0 wt % filler is preferred to minimize the possibility of such film particulate contamination and particle fragmentation of the film.

[0077] The films described herein may incorporate UV stabilizers, particularly where the intended use may include outdoor applications. Exemplary UV stabilizer additives include ultraviolet light absorbers such as Tinuvin® 329 (BASF, Ludwigshafen, Germany) and hindered amine light stabilizers such as Tinuvin® 770 or Chimassorb® 2020 (both BASF). For example, an effective UV stabilizer package for a microporous film of polypropylene copolymer PP C7054-07NA may include a combination of 0.75 wt.% Chimassorb® 2020, 0.25 wt.% Tinuvin® 770, 0.25 wt.% Tinuvin® 329, and 0.15 wt.% Irganox® B215 (antioxidant, BASF). The PP C7054-07NA microporous film without UV additive turned into powder after 8 weeks of UV aging test at 50° C. In contrast, the PP C7054-07NA microporous film with the above UV additive package did not show any visual defects such as cracks, yellowing or deformation after 8 weeks of UV aging test at 50° C.

[0078] The films described herein may incorporate other additives such as antioxidants (e.g., hindered phenolic resins such as IRGANOX® 1010 or IRGANOX® 1076 (supplied by Ciba Geigy)), phosphates (e.g., IRGAFOS® 168 (supplied by Ciba Geigy)), processing aids, UV light stabilizers, heat stabilizers, pigments, colorants, antistatic additives, flame retardants, slip agents, antiblock additives, biocides, antibiotic agents, and cleaning agents / nucleation promoters (e.g., HYPERFORM® HPN-20E, MILLAD® 3988, MILLAD® NX 8000 (available from Milliken Chemical)). Other additives may be included in the films at concentrations typically used in the art to achieve their desired purpose. In some examples, the one or more additives are included in an amount ranging from 0 to 10 wt% based on the total polymer weight of the film, or 0 to 5 wt%, 0.001 to 5 wt%, 0.001 to 3 wt%, 0.05 to 3 wt%, or 0.05 to 2 wt% based on the total polymer weight of the film. In embodiments herein where the fillers have other uses, such as colorants or pigments, they are present in a total amount of less than 5 wt%.

[0079] Laminates are also described herein. The laminate comprises a microporous film as described hereinabove and a nonwoven substrate at least partially attached to the film. As used herein, "nonwoven substrate" includes nonwoven webs, nonwoven fabrics and any nonwoven structure in which fibers or threads are inserted in other than a regular or repeating manner. The nonwoven substrates described herein can be formed by various processes, such as air-laid processes, melt-blowing processes, spunbond processes and carding processes, including bonded carded web processes. The nonwoven webs can include single webs, such as spunbond webs, carded webs, air-laid webs, spunlaced webs or melt-blown webs. However, due to the relative strengths and weaknesses associated with the various processes and materials used to manufacture nonwoven fabrics, composite structures of two or more layers can be used to achieve a better balance of properties. Such structures are often identified by letters indicating the various layers, such as SM for a two-layer structure consisting of a spunbond layer and a meltblown layer, SMS for a three-layer structure, or more commonly, SXnS structures, where S is a spunbond layer, and X can be independently a spunbond, carded, airlaid, spunlaced or meltblown layer, and n can be any number, but in practice is generally less than 5. To maintain the structural integrity of such composite structures, the layers must be bonded together. Common bonding methods include thermal calendar point bonding, adhesive lamination, ultrasonic bonding, and other methods known to those skilled in the art. All of these structures can be used in the present invention, especially when incorporated with a microporous film in the form of a laminate.

[0080] The microporous films described herein should find use in housing and construction, for example, as barrier layers for architectural envelopes such as house wraps and roofing membranes.

[0081] Also described herein are articles. The articles include the films or laminates described herein above. In some embodiments, the breathable backsheet includes the microporous films described herein above. In other embodiments, the breathable backsheet includes a laminate. The articles may be used in a variety of hygiene and medical applications. In some embodiments, the articles may include diapers, training pants, and adult incontinence articles or other similar absorbent garment articles. In other embodiments, the articles may include air masks, medical drapes, gowns, surgical garments, and protective garments or other fabric (knitted or nonwoven) articles.

[0082] This embodiment is applicable to other technologies that are susceptible to problems similar to those mentioned above. For example, the film can be used to manufacture cloth-like backsheets and medical back table (or end table) covers in operating rooms, as well as medical packaging (e.g., medical sterile pouches and sterile pouches for containing sterilized surgical equipment) and active packaging (e.g., sachets for containing desiccants in pharmaceutical tablet bottles). These are all within the scope of this embodiment. The interstitial spaces between the pores of the microporous polymeric films described herein contain thin solid segments of PP homopolymer or PP homopolymer and E / P copolymer, unlike other breathable textile candidates, where the interstitial spaces contain fibers that may or may not be bonded (typically by thermal bonding at the contact points where they meet). The advantage of the microporous polymeric films of the present invention is that the stretching process of the present invention allows for better control of the pore size and pore size distribution, so that the pores are formed by overlapping fibers, and the pore size and distribution are consistent with the number density (fibers / cm). 3The advantage of the microporous polymer film described herein is that it results in a narrower pore size distribution than other (fibrous) porous structures, which depends on the number of pores (number of pores) and the distribution of fiber diameters. Furthermore, the microporous polymer film of the present invention has smaller pores with diameters in the nanometer range, compared to fibrous materials, which have much larger pore sizes in the range of several micrometers. Although fibrous structures can be manufactured from similar hydrophobic materials, the smaller pore size of the PP-copolymer microporous polymer film can provide higher resistance to blood and body fluids, thereby allowing them to be used as breathable covers for operating room end tables. Another advantage of the microporous polymer film described herein compared to fibrous breathable films is that the handling, cutting, conversion and use of the microporous polymer film creates much less debris than is the case for fibrous structures. This makes the microporous polymer film suitable for use in ultra-clean spaces, such as in electronic processing, filtration and sterile environments in medical and pharmaceutical.

[0083] Microporous films may also find use in regular packaging (such as wraps, fruit packaging, powder packaging, packaging for sensitive electronic components, etc.) and as filtration media (for gas or liquid separation). The film may be a monolayer film or a multilayer film. As used herein, "multilayer film" refers to a film having two or more layers that are at least partially adjacent, preferably but optionally coextensive.

[0084] Some embodiments disclosed herein are described in the following clauses, and any combination of these clauses (or portions thereof) may be taken to define an embodiment.

[0085] Clause A: In certain embodiments, the invention described herein relates to a microporous polymer film comprising, consisting of, or consisting essentially of one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the microporous polymer film comprising: (i) a total amount of polypropylene homopolymer chain segments of 50 to 82 weight percent based on the weight of the microporous polymer film; and (ii) a total amount of ethylene-containing copolymer chain segments of 18 to 50 weight percent based on the weight of the microporous polymer film, at least a portion of the ethylene-containing copolymer chain segments comprising polymerized units of ethylene in an amount of at least 45 weight percent based on the weight of the ethylene-containing copolymer chain segments.

[0086] Clause B: In certain embodiments, the invention described herein relates to a microporous polymer film comprising, consisting of, or consisting essentially of one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the microporous polymer film comprising: (i) polypropylene homopolymer chain segments in a total amount of 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; and (ii) ethylene-containing copolymer chain segments in a total amount of 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film, wherein at least a portion of the ethylene-containing copolymer chain segments comprise polymerized units of ethylene in an amount of at least 55 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segments.

[0087] Clause 1: In certain embodiments, the invention described herein provides a microporous polymer film comprising, consisting of, or consisting essentially of one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the polypropylene homopolymer chain segments being in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film, and (ii) ethylene-containing copolymer chain segments. and ethylene-containing copolymer chain segments in a total amount of 18 to 50 wt % based on the weight of the microporous polymer film or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film, wherein at least a portion of the ethylene-containing copolymer chain segments contain polymerized units of ethylene in an amount of at least 45 wt % based on the weight of the ethylene-containing copolymer chain segment or at least 55 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segments.

[0088] Clause 2: The microporous polymer film of clause 1, wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of 45% to 80% by weight, or 45% to 60% by weight, based on the weight of the ethylene-containing copolymer chain segment, or 55 mol% to 86 mol% or 55 mol% to 69 mol% based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment.

[0089] Clause 3: The microporous polymer film of clause 1 or 2, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 weight percent based on the weight of the microporous polymer film, or at least 14 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0090] Clause 4: The microporous polymer film of any one of clauses 1 to 3, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 weight percent or 15 to 25 weight percent based on the weight of the microporous polymer film, or 14 to 39 mol % or 21 to 33 mol % based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0091] Clause 5: The microporous polymer film of any one of clauses 1 to 4, wherein the ethylene-containing copolymer chain segment is an ethylene-propylene copolymer chain segment.

[0092] Clause 6: The microporous polymer film of clause 5, wherein the ethylene-propylene copolymer chain segments are random ethylene-propylene copolymer chain segments.

[0093] Clause 7: The microporous polymer film of clause 5, wherein the ethylene-propylene copolymer chain segment is an ethylene-propylene diblock copolymer chain segment comprising a polypropylene block and a polyethylene block, or a diblock copolymer chain segment comprising a polypropylene block and an ethylene-propylene copolymer block.

[0094] Clause 8: The microporous polymer film of any one of clauses 5, 6 or 7, wherein the one or more ethylene-propylene copolymer chain segments are present in a total amount of 18 to 50 weight percent based on the weight of the microporous polymer film or 21 to 57 mole percent based on the molar content of polymerized monomer units in the ethylene-propylene copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0095] Clause 9: The microporous polymer film of any one of clauses 5, 6 or 7, wherein at least a portion of the ethylene-propylene copolymer chain segment comprises polymerized units of ethylene in an amount of 45% to 80% by weight, or 45% to 60% by weight, based on the weight of the ethylene-propylene copolymer chain segment, or 55 mol% to 86 mol% or 55 mol% to 69 mol% based on the molar content of polymerized units of ethylene in the ethylene-propylene copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-propylene copolymer chain segment.

[0096] Clause 10: The microporous polymer film of any one of clauses 5, 6, 7 or 8, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 weight percent based on the weight of the microporous polymer film, or at least 14 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0097] Clause 11: The microporous polymer film of any one of clauses 5, 6, 7 or 8, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 weight percent or 15 to 25 weight percent based on the weight of the microporous polymer film, or 14 to 39 mole percent or 21 to 33 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0098] Clause 12: The microporous polymer film of any one of clauses 1 to 11, having a porosity of at least 25% and a median pore diameter of at least 25 nm (4V / A, per UOP method 578-11), both characteristics measured by mercury intrusion porosimetry.

[0099] Clause 13: The microporous polymeric film of any one of clauses 1 to 12, having a permeability according to ASTM E96 / E96M-16 in the range of 10 to 100 perms.

[0100] Clause 14: The microporous polymer film of any one of clauses 1 to 13, further comprising a polypropylene homopolymer.

[0101] Clause 15: The microporous polymer film of any one of clauses 1 to 14, further comprising an ethylene-containing copolymer.

[0102] Clause 16: In one embodiment, a method of forming a microporous polymeric film, the method steps comprising: (a) one or more polypropylene copolymers, (i) one or more polypropylene homopolymer chain segments, the one or more polypropylene homopolymer chain segments having a total amount of 50 to 82 wt % based on the weight of the polypropylene copolymer or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer; and (ii) one or more ethylene-containing copolymer chain segments, the one or more ethylene-containing copolymer chain segments having a total amount of 18 to 50 wt % based on the weight of the polypropylene copolymer or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer; Also disclosed is a method that comprises, consists of, or consists essentially of: (b) providing one or more polypropylene copolymers containing polymerized units of ethylene in an amount of at least 45% by weight based on the weight of the ethylene-containing copolymer chain segment or at least 55% by mole based on the molar content of the polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units of the ethylene-containing copolymer chain segment; (c) forming a non-porous film from the polypropylene copolymer or a blend of polymers optionally containing a polypropylene copolymer; and (i) subjecting the non-porous film to successive cold and hot stretching steps including at least one cold stretching step at a temperature ranging from -20°C to 50°C, preferably from 10°C to 30°C, and (ii) at least one hot stretching step at a temperature ranging from 50°C to 150°C, preferably from 90°C to 145°C or from 100°C to 140°C, thereby producing a microporous polymer film. For example, the stretching in at least one cold stretching step can be in the machine direction. Furthermore, the stretching in the at least one thermal stretching step can be in the machine direction and / or the transverse direction.

[0103] Clause 17: The process of clause 16, wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of from 45% to 80% by weight, or from 45% to 60% by weight, based on the weight of the ethylene-containing copolymer chain segment, or from 55 mol% to 86 mol% or from 55 mol% to 69 mol% based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment.

[0104] Clause 18: The method of clause 16 or 17, wherein the microporous polymer film has a total ethylene content in polymerized form of at least 10 weight percent based on the weight of the microporous polymer film, or at least 14 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0105] Clause 19: The method of any one of clauses 16 to 18, wherein the microporous polymer film has a total ethylene content in polymerized form of 10 to 30 wt. % or 15 to 25 wt. % based on the weight of the microporous polymer film, or 14 to 39 mol. % or 21 to 33 mol. % based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0106] Clause 20: The method of any one of clauses 16 to 19, wherein the ethylene-containing copolymer chain segment is an ethylene-propylene copolymer chain segment.

[0107] Clause 21: The method of clause 20, wherein the ethylene-propylene copolymer chain segments are random ethylene-propylene copolymer chain segments.

[0108] Clause 22: The method of clause 20, wherein the ethylene-propylene copolymer chain segment is an ethylene-propylene diblock copolymer chain segment comprising a polypropylene block and a polyethylene block, or a diblock copolymer chain segment comprising a polypropylene block and an ethylene-propylene copolymer block.

[0109] Clause 23: The process of any one of clauses 20, 21 or 22, wherein the ethylene-propylene copolymer chain segments are present in a total amount of from 18 to 50 weight percent based on the weight of the polypropylene copolymer or from 21 to 57 mole percent based on the molar content of polymerized monomer units in the ethylene-propylene copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer.

[0110] Clause 24: The process of any one of clauses 20, 21, 22 or 23, wherein at least a portion of the ethylene-propylene copolymer chain segment comprises polymerized units of ethylene in an amount of from 45% to 80% by weight, or from 45% to 60% by weight, based on the weight of the ethylene-propylene copolymer chain segment, or from 55 mol% to 86 mol% or from 55 mol% to 69 mol% based on the molar content of polymerized units of ethylene in the ethylene-propylene copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-propylene copolymer chain segment.

[0111] Clause 25: The method of any one of clauses 20, 21, 22 or 23, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 weight percent based on the weight of the microporous polymer film, or at least 14 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0112] Clause 26: The method of any one of clauses 20, 21, 22 or 23, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 weight percent or 15 to 25 weight percent based on the weight of the microporous polymer film, or 14 to 39 mole percent or 21 to 33 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

[0113] Clause 27: The polypropylene copolymer has a melt flow rate, measured according to ASTM D-1238, condition L, at 230°C and 2.16 kg, of 0.1 to 100 g / 10 min, and a melt flow rate of 0.9 g / cm 3 27. The method of any one of clauses 16 to 26, having a density of greater than 100%.

[0114] Clause 28: The method of any one of clauses 16-27, wherein the polypropylene copolymer is blended with a polypropylene homopolymer to form a polymer blend prior to forming the non-perforated film.

[0115] Clause 29: The process of any one of clauses 16 to 28, wherein the polypropylene copolymer is blended with an ethylene-containing copolymer, preferably an ethylene-propylene copolymer, to form a polymer blend prior to forming the non-porous film.

[0116] Clause 30: The method of any one of clauses 16 to 29, wherein forming the non-porous film is accomplished by extruding the polypropylene copolymer or polymer blend thereof in a molten state.

[0117] Clause 31: The method of any one of clauses 16 to 30, wherein the non-porous polymer film has a morphology characterized by a majority polymer phase of polypropylene, a plurality of minor polymer domains of an ethylene-containing copolymer within the majority polymer phase, and inclusion phases of a predominant polypropylene phase within the minor polymer domains.

[0118] Clause 32: In some embodiments, the method of any one of clauses 16 to 31 further comprises the step of: annealing It is executed without any steps.

[0119] Clause 33: The method of any one of clauses 16 to 32, wherein at least one cold stretching step stretches the film by at least 10% in at least one direction, and at least one hot stretching step stretches the film by at least 20% in at least one direction.

[0120] Clause 34: In some embodiments, the method of any one of clauses 16 to 33 further comprises the step of: annealing or Heat Set It is executed without any steps.

[0121] Clause 35: In some embodiments, the method of any one of clauses 16-34 is a continuous process for producing a microporous polymeric film.

[0122] Clause 36: The method of any one of clauses 16 to 351, wherein the microporous polymer film has a porosity of at least 25% and a median pore diameter of at least 25 nm (4 V / A, per UOP method 578-11), both characteristics measured by mercury intrusion porosimetry.

[0123] Clause 37: The method of any one of clauses 16-36, wherein the microporous polymeric film has a permeability according to ASTM E96 / E96M-16 in the range of 10 to 100 perms.

[0124] Clause 38: A microporous polymer film formed by the method of any one of clauses 16 to 37.

[0125] Clause 39: The microporous polymer film formed by the method of any one of clauses 16-37, wherein the non-porous polymer film has a morphology characterized by a majority polymer phase of polypropylene, a plurality of minor polymer domains of an ethylene-containing copolymer within the majority polymer phase, and inclusion phases of a predominant polypropylene phase within the minor polymer domains. In one embodiment, the non-porous polymer film has a morphology characterized by a majority polymer phase of polypropylene, a plurality of minor polymer domains of an ethylene-propylene copolymer within the majority polymer phase, and inclusion phases of a predominant polypropylene phase within the minor polymer domains.

[0126] Clause 40: The microporous polymeric film of any one of clauses 1 to 15, which is or is a component of a roof membrane.

[0127] Clause 41: The microporous polymer film of clause 40 having a thickness of at least 100 μm, or having a thickness of at least 250 μm.

[0128] Clause 42: The microporous polymeric film of any one of clauses 1-15, which is at least a portion of a medical packaging or active packaging article or a medical back table cover.

[0129] Clause 43: A medical packaging or active packaging article or a medical back table cover comprising the microporous polymeric film of any one of clauses 1 to 15.

[0130] Clause 44: A medical packaging or active packaging article or medical back table cover comprising a microporous polymer film, the microporous polymer film comprising one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the microporous polymer film comprising: (i) polypropylene homopolymer chain segments in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; and (ii) ethylene-containing copolymer chain segments in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. and ethylene-containing copolymer chain segments in a total amount of 18-50 wt% based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film, and at least a portion of the ethylene-containing copolymer chain segments comprise polymerized units of ethylene in an amount of at least 45 wt%, such as 45-80 wt%, preferably 45-60 wt%, based on the weight of the ethylene-containing copolymer chain segments, or at least 55 mol%, such as 55-86 mol%, based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segments.

[0131] Clause 45: The medical packaging or active packaging article or medical back table cover of clause 44, wherein the microporous polymeric film has a barrier against microorganisms equivalent to the maximum penetration, calculated %Pmax, as defined by ASTM F2638-18, of <10%, preferably <5% or <1%.

[0132] Clause 46: The microporous polymer film has a melting point of 10 to 35,000 seconds / 100 cm 3 4. Medical packaging of clause 44 or 45 having a Gurley Gauge breathability of 100% or less and controlling the inflow or outflow of air or one or more gases into or out of the package.

[0133] Clause 47: The medical packaging of any one of clauses 44-46, wherein the microporous polymeric film is thermoformable and heat sealable.

[0134] Clause 48: A microporous polymeric film comprising a polypropylene copolymer made from the reaction product of a polypropylene homopolymer and an ethylene-propylene copolymer.

[0135] The present invention is further defined in the following examples, in which all parts and percentages are by weight unless otherwise specified. It should be understood that these examples, while illustrating preferred embodiments of the present invention, are given by way of illustration only and should not be construed as limiting in any way. From the above discussion and these examples, one skilled in the art can ascertain the essential characteristics of the present invention, and can make various modifications and alterations to the present invention to suit various applications and conditions without departing from the spirit and scope thereof. EXAMPLES

[0136] material Homopolymer polyethylene is referred to herein as PE. The homopolymer-PE used herein is HDPE 6400, a resin available from Dow Chemical Company, Midland, MI, USA.

[0137] Homopolymer polypropylene is referred to herein as PP. The homopolymer-PP used herein is PP H314, a resin available from Braskem, USA (Philadelphia, PA, USA).

[0138] Ethylene-propylene copolymers are referred to herein as EP. Numerous EP and PP-EP copolymers and homopolymer-PP blends with EP or PP-EP copolymers are described herein, for example, as detailed in Examples 2 and 6.

[0139] The polypropylene copolymer resin used in this study is PP C7054-07NA, a PP-EP copolymer containing PP chain segments and ethylene-propylene random copolymer chain segments, purchased from Braskem USA. PP C7054-07NA resin contains 32.9 wt% ethylene-propylene copolymer (and 100-32.9=67.1% PP), while the ethylene content in the ethylene-propylene copolymer chain segments is 49.7 wt%. It has a tensile strength of 0.9 g / cm. 3 and a melt index of 7 g / 10 min at 230° C. and 2.16 kg. Other PP copolymer resins are listed in Table 2.

[0140] The term "Tyvek" by itself refers to Tyvek housewrap (approximately 32% porosity; average pore diameter of 37 nm) and the term "Tyvek 1073B" refers to a special grade of Tyvek nonwoven used as a medical packaging layer (approximately 65% ​​porosity; average pore diameter of 2500 nm).

[0141] Cast Film PP C7054-07NA resin cast films were produced on a film casting line consisting of a 1.25 inch Killion single screw extruder and a 30 inch wide casting die with a 30 mil die gap. A typical temperature profile (for extruder zones 1-8) of a pilot scale extrusion line using a 30 inch die used to produce the (co)polymer cast films described herein can be as follows (e.g., for PP copolymer films): 180, 200, 210, 210, 210, 210, 210, 210°C.

[0142] Uniaxial and biaxial stretching of film on an Iwamoto biaxial stretcher Uniaxial stretching (machine direction orientation, MDO) procedure: The film was cut to a pre-determined dimension. Adhesive tape was attached to both ends of the film (in the cross direction) and it was fitted into a specially designed sample holder. The sample holder plate was fastened together with five bolts. The legs of the sample holder were then attached onto the back of the grips of an Iwamoto biaxial stretcher (BIX-703, Iwamoto Seisakusho). The film was subjected to uniaxial cold stretching in the machine direction. Afterwards, the door of the sample chamber was closed and the sample chamber was heated to 100°C and subsequently held at this temperature for 1 minute. The film was then subjected to uniaxial hot stretching in the machine direction. The cold stretching degree was

number

number

[0143] After stretching, the film turned white due to the formation of a microporous structure.

[0144] For biaxial stretching, the PP-based film was cut to a predetermined dimension (70 mm x 70 mm) and then loaded onto the grips of an Iwamoto biaxial stretcher. The film was simultaneously biaxially stretched in both directions at room temperature and then heated to 100°C. After holding at 100°C for 1 minute, the film was simultaneously biaxially stretched in both directions at elevated temperature. The degree of stretching for biaxial stretching is defined similarly to that for uniaxial stretching.

[0145] Differential Scanning Calorimetry (DSC) A portion of the sample was weighed and placed into an aluminum hermetically sealed DSC pan (P / N 900793.901 pan and 900794.901 lid) and sealed. Sample weights were approximately 1-4 mg for each sample. Samples were scanned in a TA Instruments Q2000 DSC (Differential Scanning Calorimeter) (P / N 970001.901) (s / N 2000.0877) equipped with an autosampler, a 50 ml / min nitrogen purge, and a mechanical cooling accessory. Run parameters for the heat-cool heating cycle were -20°C to 200°C at 10°C / min with a sampling interval of 0.1 sec / pt. Scans were analyzed using Universal Analysis V4.7A TA Instruments software. Melting points obtained from the DSC scans are shown as output from the instrument software and correspond to a plot of the peak temperature in the heat flow versus temperature in the second heating cycle.

[0146] Mercury intrusion porosimetry Mercury intrusion porosimetry analysis was carried out according to ASTM D4404-10 on a Micromeritics Autopore IV 9520. Prior to mercury analysis, samples were mechanically degassed at room temperature under vacuum to remove any physisorbed species (i.e., moisture) from the sample surface.

[0147] Test conditions included Hg filling pressure 0.50 psia, Hg contact angle 130°, Hg surface tension 485 dynes / cm, Hg density 13.53 g / mL, 30 min evacuation time, small bore hardness tester with 5 cm3 valve (solid type: 0.392 stem volume), 30 s equilibration time, 92 point pressure table (75 intrusion plus 17 extrusion pressure points) and mechanical evacuation <50 μm Hg. Low-high pressure crossover was collected at approximately 46 psia (3.8 μm). The pressure table used was created to allow incremental distribution of pressure on a log scale from 0.5 to 60,000 psia and is used to detect pore sizes (diameters) from 0.003 to 400 μm in diameter. As the pressure is increased stepwise from vacuum to a maximum of nearly 60,000 psia, mercury is forced into the smaller pores. According to UOP method 578-11, the average pore diameter (4V / A) is calculated based on the assumption that all pores are right circular cylinders with length (l) and diameter (d). The total pore volume (V=πd 2 When the average pore diameter (d) is divided by the total pore area (=πdl), the average pore diameter (d) is 4V / A.

[0148] To ensure that the instrument was functioning properly, a silica-alumina reference material, lot A-501-46, was analyzed. The reported median pore diameter (by volume) of the reference sample is 0.0072±0.0005 μm. Autopore reported the median pore diameter (by volume) to be 0.0072 μm.

[0149] Scanning Electron Microscopy (SEM) The samples were freeze-fractured and mounted on SEM stubs by carbon tape, then coated with 30 nm of gold to mitigate charging. The top and fractured surfaces of each sample were imaged at specific locations and at various magnifications ranging from 5000x to 10,000x utilizing an FEI Nova NanoSEM model 600 in secondary electron (TLD) imaging mode. To prevent beam damage to the samples, the accelerating voltage was set within 3-5 kV with a spot diameter of 3-4 (scale of the spot diameter knob) at a working distance (distance from the last pole piece of the lens to the sample when the image is in focus) of approximately 5 mm.

[0150] Transmission Electron Microscopy (TEM) The PP copolymer film was cut into small trapezoids so that sections could be collected. Sections approximately 100 nm thick were collected at ambient temperature using a diamond knife on a Leica EM UC7 microtome and placed on a 400 mesh virgin TEM grid for observation. The microtomed films were stained with the vapor phase of a 0.5 M (mol / L) aqueous solution of osmium tetroxide for 3-5 min at ambient temperature. TEM images were collected on an FEI Tecnai 12 operated at an accelerating voltage of 120 kV using a Gatan MultiScan CCD camera.

[0151] X-ray diffraction technology Small angle X-ray scattering (SAXS) and wide angle X-ray diffraction (WAXD) studies were performed at the Advanced Photon Source (Argonne National Laboratory) using DND-CAT (5-ID-D beamline). As X-ray source, a standard APS Undulator A was used with an X-ray energy setting of 17 keV (λ = 0.7923 Å). All samples were performed in normal beam transmission mode. Detector calibration was performed using silver behenate and lanthanum hexaboride standard reference materials. The two-dimensional scattering patterns were reduced to one-dimensional data sets of scattering intensity versus scattering vector by radial integration of the two-dimensional images. Reduction and analysis of the one-dimensional patterns was performed using the commercially available software package JADE.

[0152] Water Vapor Transmission Rate (WVTR) Measurement (ASTM F1249) A Mocon 3 / 33 model MG module was used to evaluate the WVTR for this study. Test conditions were 37.8°C / 100% RH per ASTM method F1249. 2Film samples were prepared using a 76.2 μm (3 mil) aluminum foil / acrylic adhesive mask to center the test area to approximately 2 inches in diameter. The film sample divided the test cell into two halves. The ends of the test cell were securely sealed to prevent outside air from leaking into the cell. This was accomplished with silicone grease to aid in sealing the film to the cell (carrier gas side) and a rubber O-ring was used to seal the outer cell cover or water vapor side. Standard sample areas were 50 cm2. 2 During a typical test, water vapor (test gas) entered the outer half of the test cell continuously. This gas could be either 100% relative humidity (wet sponge) or generated by the instrument at 30-90% relative humidity. The water vapor permeated the film sample and was then transported in the carrier gas (dry nitrogen) to the IR sensor, which generated a current directly proportional to the amount of water vapor passing through the film. A computer collected the data from the IR sensor and calculated a final value describing the water vapor transmission rate of the test material. WVTR data is expressed in grams / 24h m 2 The normalized WVTR takes into account the film thickness and is reported in units of g cm / 24h m 2 It is reported as:

[0153] Water Vapor Transmission (ASTM E96 / E96M-16) Water vapor transmission was determined according to ASTM E96 / E96M-16, Standard Test Method for Water Vapor Transmission of Materials, Desiccant Method. The specimens were cut into circular disks with a diameter of 90.3 mm. The pocket in the dish was filled with calcium chloride to within 6.4 mm (1 / 4 in.) of the specimen. The specimen was then fitted onto the dish just above the pocket with a metal plate leaving the diameter of the specimen exposed to the environment at 76.1 mm. The specimen was prepared with the outer surface of the product facing the desiccant. The assembly was then placed in a controlled chamber operating at a temperature and relative humidity (RH) of 23 ± 2 °C and 50 ± 5%, respectively. The assembly was then weighed periodically. Water vapor transmission data is reported in units of "perms", grams / 24 h m 2It is possible to convert the permeation to water vapor permeation in units of 10 / s. Any use of the unit "perm" herein means US perm. 1 US perm = 5.72 x 10 -8 g / (Pa·s·m 2 ).

[0154] Gurley Hill Porosity (Gurley Breathability) To measure the Gurley flow value of the microporous films, a Genuine Gurley Instruments Densometer and a Lorentzen & Wettre L&W Model 121D Densometer were used. The densometer measures the flow rate of gas (e.g., 100 cm, which is the conventional flow rate used in this test). 3 The time required for a given volume of air (100 cm2) to pass through a 1 inch diameter area of ​​the film (and with a specific pressure gradient, conventionally about 4.9 inches of water) is recorded. The test procedure conformed to the TAPPI T-460 OM-11 method. Prior to testing, a confirmation test was performed by using a calibration plate with a known value of Gurley air permeability (19.2 seconds). The calibration plate allows for a 100 cm2 permeability in 19.2 seconds or less. 3 Once confirmed, the microporous film samples were tested. Even though permeability is dependent on the area of ​​the test sample and the pressure, these values ​​are standardized for the instrument, so the results are traditionally reported in s / 100cm. 3 reported in units of 100 cm of air or 3 In this specification, Gurley Hill Porosity is described as Gurley Air Permeability and is reported simply as s / 100 cm as is common in the art. 3 will be reported.

[0155] Grab Tensile Test Grab tensile tests were performed on an Instron Tester. The test procedure followed ASTM D 5034-09(2013) test method. The grab specimens were gripped at the center of the specimen width to ensure the top and bottom portions were not gripped equally. The crosshead speed was 12 inches / minute for all experiments. The Instron reports the tensile strength (Newtons per unit width) and elongation (%) at peak load.

[0156] Nuclear magnetic resonance (NMR) spectroscopy Approximately 0.25 g of sample was cut into small pieces and inserted into a 10 mm NMR tube. 2.6 ml of tetrachloroethane-d2 (TCEd2) containing 10 mM relaxation agent was added. The sample was then heated at 115°C. The following parameters were used on a Bruker 600 MHz spectrometer equipped with a 10 mm cryogenic probe: 13 C NMR and diffusion measurements (translational diffusion) (to confirm homopolymer or blend) were performed. Repeat time: 15 seconds Number of scans: 1536 90° pulse: 12ms Spectral width: 240ppm Temperature: 115℃ Spectral center: 90ppm

[0157] Gel Permeation Chromatography (GPC) Samples were dissolved in the carrier liquid at a concentration of 1 mg / ml by shaking in 1,2,4-trichlorobenzene (TCB) containing 200 ppm butylhydroxytoluene (BHT) at 160 °C for 2 h. GPC was performed on a PolymerChar High Temperature LC system operated in GPC mode. The injection volume was 300 μl. The flow rate was 1 ml / min. The eluent was TCB containing 200 ppm BHT. Separation was performed on two 7.5 × 300 mm PL-Gel mixed B columns (Agilent). An integrated IR5 detector in the PolymerChar HTLC (high temperature liquid chromatography) was used for detection. A series of 16 polystyrene (PS) narrow molecular weight distribution standards (Agilent Corporation) were used for molecular weight calibration. The calibration range was 0.58 to 3750 kg / mol, and the calibration curve was a least-squares fit to a third-order polynomial. Thus, the reported molecular weights are PS equivalent molecular weight values. Once confirmed, the microporous film samples were tested.

[0158] Microbial Barrier Test (ASTM F2638-18) The Microbial Barrier Test (ASTM F2638-18) uses aerosol filtration to measure the performance of porous packaging materials as a surrogate microbial barrier and is applicable to porous materials used to package devices for terminally sterilized medical treatments. It measures the aerosol filtration performance of porous packaging materials by generating a defined aerosol of 1.0 μm particles and evaluating the filtration efficiency of the material using a single or dual particle counter. The test results are reported as a calculated %P max P is recorded as the highest percent concentration of particles in the filtrate aerosol (particles that remain aerosolized after passing through the specimen) when the specimen is tested over a range of pressure differentials or air velocities. max A lower value means a better barrier to particulate matter or microorganisms.

[0159] Example 1 This example is for a homopolymer PP film before stretching. annealingThe effect of stretching is investigated. Table 1 shows the results (before stretching). annealing The drawing conditions and corresponding porosity and pore size (median pore diameter) of homopolymer polypropylene, PP H314, after drawing both with and without drawing are shown in Table 1. The designation CSXX-HSYY means that the film was subjected to cold drawing of XX% followed by hot drawing of YY%.

[0160] [Table 1]

[0161] Table 1 shows the results of the experiments performed at temperatures near the melting point of PP for an extended period of time to achieve the desired pore size and porosity. annealing is required. annealing The PP H314 sample without stretching did not turn white after stretching, and correspondingly, the film showed very low porosity (2-4%), as shown in Table 1. In contrast, the PP H314 sample without stretching at 150 °C for 24 h showed very low porosity (2-4%). annealing When the same stretching conditions were performed, the film immediately turned white and had a porosity of 20-24%. Similar results were obtained for films of homopolymer PE (HDPE 6400).

[0162] In addition, the film annealing In the absence of this, blends of homopolymer PE (HDPE 6400) and homopolymer PP (PP H314) were investigated to see if polymer incompatibility would aid in pore formation. Blends of homopolymer polypropylene and homopolymer polyethylene were prepared in a twin screw extruder and extruded into films. annealing Extruded films of blend ratios (homopolymer polyethylene to homopolymer polypropylene) of 100:0, 90:10, 80:20, 70:30, 50:50, 30:70, 20:80, 10:90 and 0:100 were prepared as above without performing the step and then subjected to successive cold (CS) and hot (HS) uniaxial stretching (25% cold stretch at room temperature at 100 mm / sec followed by 100% hot stretch at 100° C. and 5 mm / sec). annealingWhen this was not performed, no pore formation was observed for the films of these PP / PE homopolymer blends.

[0163] Long-term annealing Time is an issue in terms of the desired objective of running a continuous production line to produce microporous film. Ideally, annealing A continuous extrusion and pore forming process in one continuous manufacturing line without the need for hold periods for extended steps is preferred.

[0164] Example 2 One of the objects of the present invention is to prevent any heat treatment before or after film stretching. annealing The present invention provides a method for producing a film in which pores can be formed during film stretching without requiring any additional steps. annealing Eliminating the steps allows for a continuous manufacturing process. annealing Reduce production time or preferably from similar manufacturing processes of polyethylene or polypropylene homopolymers. annealing To completely eliminate this step, we investigated the microphase separation-induced pore formation in homopolymer polypropylene. For this reason, PP copolymers composed of homopolymer polypropylene (PP) chain segments and ethylene-propylene (EP) copolymer chain segments were prepared and extruded into films.

[0165] In order to define the effective parameters and scope of the present invention, four different reactor grade PP copolymers were evaluated. The characteristics of the various PP copolymers are shown in Table 2 (melt flow rate, EP copolymer content (isotactic PP content is 100-EP content) and ethylene and propylene content in EP copolymer chain segments).

[0166] [Table 2]

[0167] Films of these PP copolymers were prepared as described above and then subjected to successive cold (CS) and hot (HS) uniaxial stretching (25% CS at 100 mm / s followed by 100% HS at 100° C. and 5 mm / s). The film characteristics (average pore size, porosity and WVTR) are shown in Table 3.

[0168] [Table 3]

[0169] The comparative examples PP TI4020N and PP INSPIRE® film 114 were found to have very low average pore diameter (8-12 nm) and very low film porosity (7-10%), and these film characteristics correspond to very low water vapor transmission rate and very low water vapor transmission. Both samples are unsuitable for their intended purpose as breathable films. On the other hand, the inventive examples PP C700-35N and PP C7054-07NA films had similar target ranges of average pore diameter and film porosity as commercial Tyvek®, and film characteristics such as water vapor transmission rate and water vapor transmission, suggesting that both these samples are suitable as breathable films.

[0170] Example 3 PP C7054-07NA resin, a PP copolymer containing homopolymer polypropylene chain segments and ethylene-propylene copolymer chain segments, was selected for further studies to optimize the stretching conditions to explore the range of microporous film characteristics accessible by this approach. The initial thickness of the PP C7054-07NA resin film before stretching was 203 μm.

[0171] As described above, films were prepared from PP C7054-07NA and subjected to successive cold and hot uniaxial stretching at various process conditions as listed in Table 4. The film characteristics (pore size and porosity) were then evaluated to confirm the practical process parameters.

[0172] [Table 4]

[0173] Table 4 shows that the stretching conditions can be optimized to adjust the desired porosity and average pore diameter. Multiple comparisons can be performed for a particular stretching variable (cold stretch (%), hot stretch (%), and hot stretch temperature (°C)) (by controlling two of the three variables to be constant while varying the third variable). For example, one such series is illustrated by Samples 1-4, which show the effect of hot stretch temperature (°C) when the range of room temperature cold stretch and the range of hot stretch are held constant (25% and 50%, respectively). Increasing the hot stretch temperature in the temperature range of 60-120°C increases the porosity and pore size (median pore diameter). Another such series is illustrated by Samples 11-16, which show the effect of hot stretch at 100°C after a 25% room temperature cold stretch. Again, there is an increase in porosity and pore size (median pore diameter) with increasing hot stretch in the range of 25-100% hot stretch, but the trend recedes at higher hot stretches (200 or 300%).

[0174] Example 4 This example investigates the performance of PP copolymer uniaxially stretched microporous film. Example 3 demonstrated the effect of film stretching conditions on pore formation (in terms of porosity (%) and average pore diameter (nm)). In Table 4 above, the degree of hot stretching clearly has a significant effect on porosity and average pore diameter, so this series (samples 11-14) was selected for further study, including physical properties and performance data.

[0175] The PP C7054-07NA resin microporous films were subjected to the same cold stretch degree (25%) at 25°C, while the hot stretch degree ranged from 25% to 100% at 100°C. The initial thickness of the PP C7054-07NA resin film before stretching was 203 μm, and the final film thickness after stretching under various stretching conditions are listed in Table 5.

[0176] Mercury porosimetry was used to measure the average pore diameter and porosity of the stretched PP C7054-07NA films of this series, and the results are summarized in Tables 4 and 5. The pore distribution of the PP C7054-07NA microporous films for this series is illustrated in Figure 1B and compared to that of Tyvek® in Figure 1A. Note that the y-axis scale is different in Figure 1A compared to that shown in Figure 1B.

[0177] [Table 5]

[0178] Table 5 and Figures 1A and 1B show that under proper stretching conditions, PP C7054-07NA microporous film can exhibit greater pore size and porosity than Tyvek® housewrap.

[0179] [Table 6]

[0180] As shown above (Table 4, Example 3), when the hot stretch range increases from 25 to 100%, both the porosity and pore size (average pore diameter) increase. It is also expected that the increase in both porosity and average pore diameter leads to an increase in water vapor transmission ("perm") (Table 6). As shown in Table 6, by adjusting the pore diameter of PP C7054-07NA microporous film, the water vapor transmission can be varied from 14 perms to 82 perms (ASTM E96). It is noted that the water vapor transmission for Tyvek® house wrap with similar thickness is about 60 perms. Table 6 also shows the Gurley air permeability of PP C7054-07NA microporous film, which indicates that C7054-07NA microporous film may have a better barrier to air flow, and therefore they may be a better choice for improving the energy efficiency of a home than, for example, Tyvek®.

[0181] Example 5 This example considers the morphology of PP copolymer films. Prior art blends of homopolymer polypropylene and minority homopolymer polyethylene produce films with microphase separation resulting in incompatible regions of polyethylene within the polypropylene matrix (PP / PE). The polypropylene copolymers disclosed herein were cast as films and investigated with the aim of producing microphase separation within the incompatible EP regions within the polymer film. Such microphase separation results in inclusion phases within the incompatible regions. The morphology of these films before and after stretching was investigated by SEM and TEM.

[0182] FIG. 2 shows SEM images of the film cross-section. FIG. 2A shows the cross-section of an unstretched PP C7054-07NA film (indicated by the 20 micron scale bar), while FIG. 2B and 2C show a stretched PP C7054-07NA film by 25% cold stretch and 50% hot stretch (100° C.). Indicated by the 20 micron scale bar in FIG. 2B compared to the 5 micron scale bar in FIG. 2C. In the unstretched PP C7054-07NA film in FIG. 2A, microphase separation and associated domain formation can be seen with domain diameters ranging from a few hundred nanometers to about 3 microns. In FIG. 2B and 2C, the PP C7054-07NA film shows annealing was not performed, but was directly subjected to cold stretching (25%) at a stretching speed of 100 mm / s, followed by hot stretching at a stretching speed of 5 mm / s and a temperature of 100° C. As can be seen from the SEM images of the film cross section in Figures 2B and 2C, many pores are formed by the 25% cold stretch and 50% hot stretch.

[0183] Figure 3 shows SEM images of the film surface. Figures 3A and 3B show the unstretched PP C7054-07NA film, with the 20 micron scale bar in Figure 3A compared to the 10 micron scale bar in Figure 3B. Figures 3C and 3D show the stretched PP C7054-07NA film by 25% cold stretching at a stretching speed of 100 mm / s followed by 50% hot stretching (100°C) at a stretching speed of 5 mm / s, with the 20 micron scale bar in Figure 3C compared to the 10 micron scale bar in Figure 3D. Before stretching, the film surface is very smooth (Figures 3A and 3B). In contrast, pores can be clearly observed on the surface of the stretched PP C7054-07NA film (Figures 3C and 3D).

[0184] Figure 4 shows TEM images of the film before and after stretching. Figures 4A and 4B show PP C7054-07NA film before and after stretching, respectively (25% CS; 50% HS, as above), with both Figures 4A and 4B indicated with a 1 micron scale bar. Figures 4C and 4D show PP INSPIRE® 114 film before and after stretching, respectively (25% CS; 50% HS, as above), with both Figures 4C and 4D indicated with a 0.2 micron scale bar.

[0185] In the unstretched film of PP C7054-07NA in FIG. 4A, microphase separation and associated domain formation can be easily seen, with domain diameters ranging from a few hundred nanometers to about 3 microns. The TEM images in FIGS. 4A and 4B suggest that the cavitation process is nucleated in the ethylene-propylene (EP) domains for the PP C7054-07NA film. Without wishing to be bound by theory, it is believed that the inclusion morphology of the PP microphase in the EP domains within the PP matrix allows the stretching force to be effectively transferred to the microphase domains, which are then split into small fragments to initiate pore formation and growth. In contrast, after stretching of the PP INSPIRE® 114 film, the EP domains of the PP INSPIRE® 114 film only showed elongation along the stretching direction (FIGS. 4E and 4F). There was no pore formation.

[0186] Further evidence of the different response to stretching between films of PP C7054-07NA or PP C700-35N compared to PP TI4020N or PP INSPIRE® 114 was observed in wide angle X-ray scattering (WAXS) studies. The WAXS pattern correlates with the Bragg diffraction of X-rays by the polypropylene crystalline lattice and provides information regarding the crystalline composition, crystalline orientation and relative amount of crystallinity.

[0187] Figure 5 shows the WAXS patterns of two different PP copolymers, PP C7054-07NA and PP TI4020N films. The samples for each copolymer included unstretched films and samples stretched by 25% cold stretch at room temperature and 100% hot stretch at 100°C. No significant change in the crystal structure was observed for the PP C7054-07NA resin film before and after stretching the film (Figures 5A and 5B, respectively). The same observation was also made for the PP C700-35N resin film (not shown). As shown in Figures 5C and 5D, significant orientation was observed for the PP TI4020N resin film as the crystal structure rotated and rearranged into a fibrillar structure, with strong diffraction intensity emission in the (110), (040), (130) and (131) planes. Similar observations were also made for the PP INSPIRE® 114 resin film (not shown). From the above WAXS results, it is inferred that the stretching force was applied to the crystalline polypropylene structure of PP TI4020N resin film and PP INSPIRE®114 resin film, but during the stretching process of PP C7054-07NA resin and PP C700-35N resin film, the stretching force was transferred to the EP phase to initiate and grow pores. Such a mismatch results in high porosity for both PP C7054-07NA resin and PP C700-35N resin microporous film, but low porosity for both PP TI4020N resin film and PP INSPIRE®114 resin microporous film.

[0188] Example 6 annealingPore ​​formation via stretching of films without any modification has been previously demonstrated (Examples 2-4 above) using a PP copolymer (see PP C7054-07NA microporous film above). Further blending of this PP copolymer as the major component with homopolymer-PP, PP H314 (as a minor component) was also investigated (Table 7). Films were prepared as described above and stretched under the following stretching conditions: 25% cold stretch (room temperature) at a stretch rate of 100 mm / s, followed by 100% hot stretch (100° C.) at a stretch rate of 5 mm / s.

[0189] [Table 7]

[0190] Blending increasing amounts of homopolymer-PP with PP C7054-07NA copolymer followed by cold and hot stretching processes resulted in progressively lower porosity and lower average pore diameters in the stretched microporous films until no pore formation was obtained with 40% additional homopolymer-PP.

[0191] Similarly, annealing Pore ​​formation via stretching of films without stretching was previously demonstrated with another PP copolymer (see PP C700-35N microporous film, Table 3) (Example 2). Further blending of this PP copolymer as the major component with homopolymer-PP, PP H314 (as a minor component) was also investigated (Table 8).

[0192] [Table 8]

[0193] Blending 20 wt% homopolymer PP H314 with PP C7054-07NA using a twin-screw extruder followed by film production also reduced the inclusion morphology, such that upon stretching, the majority of the microphase domains extended only along the stretch direction (see, for example, TEM in Figures 6A and 6B).

[0194] The results for the films from blends of PP C700-35N with homopolymer-PP were similar to those for the films from blends of PP C7054-07NA with homopolymer-PP.

[0195] As stated above, annealing Pore ​​formation via unperformed film stretching has been demonstrated for PP copolymers (see PPC7054-07NA microporous film above). annealing Further blending of this copolymer as a major component with a PP copolymer, PP TI4020N (as a minor component) was also demonstrated to form pores via film stretching where no stretching was performed (Table 9).

[0196] [Table 9]

[0197] Blends of PP C700-35N and PP TI4020N can also be used to form films that can be stretched (without prior annealing) to produce microporous films.

[0198] Other polymer blends were evaluated as follows: VERSIFY® 2000 resin (Melt flow rate = 2g / 10min @ 230°C, 2.16kg) is an ethylene-propylene random copolymer with a composition of 94% P / 6% E (propylene rich). VERSIFY® 2400 resin (Melt flow rate = 2g / 10min @ 230°C, 2.16kg) is also an ethylene-propylene random copolymer with a composition of 86% by weight P / 14% by weight E (propylene rich). In each case, two blend ratios (85:15 and 70:30) with homopolymer PP (PP H314) were prepared. PP H314 was the major component in all blends. The blends were annealingThe films without stretching were subjected to CS25-HS100 stretching conditions (above). None of these PP / EP blends formed pores after the stretching process. This may be due to the high content of propylene segments in the VERSIFY® 2000 and VERSIFY® 2400 resins. The propylene segments have good compatibility with the PP matrix and therefore cannot induce sufficient phase separation in the PP H314 resin.

[0199] The 13C04R21 experimental resin (melt flow rate = 18 g / 10 min at 230°C, 2.16 kg) is an isotactic PP diblock block copolymer with a 50:50 ratio of PP:EP components in the copolymer, the EP copolymer block containing 14 wt% E and 86 wt% P (total ethylene content of the resin is 7 wt%). Blends of this diblock copolymer with homopolymer PP (PP H314) were prepared in ratios of 85:15, 80:20, 70:30 and 60:40 (predominant PP), annealing The films without were subjected to CS25-HS100 stretching conditions (above). None of these PP / EP blends formed pores after the stretching process. The EP block in this experimental grade resin contains only 14 wt% ethylene, producing a PP-rich EP block. As a result, it is believed that the EP and iPP blocks have good compatibility with the homopolymer PP resin, and therefore the EP block is not able to initiate sufficient phase separation in the film.

[0200] INTUNE® D5545.00 (Melt flow rate = 9.5 g / 10 min @ 230°C, 2.16 kg) is another isotactic PP diblock block copolymer having a 50:50 ratio of PP:EP copolymer, but the EP copolymer block is ethylene rich, containing 92 wt% E and 8 wt% P (total ethylene content of the resin is 46 wt%). annealingBy stretching the film without stretching (CS25-HS100 stretching conditions in Example 6 above), only minimal pore formation is achieved: 13.6% porosity and 14.1 nm average pore diameter. The diblock copolymer film is not suitable for its desired purpose as a house wrap material. Blends of this diblock copolymer with homopolymer PP (PP H314) were prepared in ratios of 85:15, 80:20, 70:30 and 60:40 (predominant PP) and annealing The untreated films were subjected to the CS25-HS100 stretching conditions (above) of Example 6. None of these PP / EP copolymer blends formed pores after the stretching process.

[0201] NORDELL® 3722P is an EPDM (ethylene-propylene diene monomer) copolymer with a composition of 28.5 wt% propylene, 71 wt% ethylene and 0.5 wt% ENB (ethylidene norbornene). Blend ratios of 90:10, 80:20 and 70:30 (polypropylene rich), PP-H314:NORDELL® 3722P, the primary homopolymer PP blends with NORDEL® 3722P, were investigated. annealing The untreated films were subjected to the CS25-HS100 stretching conditions (above). None of these PP / EP copolymer blends formed pores after the stretching process.

[0202] In addition, ethylene acrylic acid (PRIMACOR® 1410 resin: 90.3 wt. % E, 9.7 wt. % acrylic acid) was evaluated (Melt flow rate at 230° C., 2.16 kg=1.5 g / 10 min). The blend was 85 wt. % PP H314 resin and 15 wt. % PRIMACOR® 1410 resin. Under the same stretching conditions, this blend failed to show pore formation. PRIMACOR® 1410 resin was incompatible with PP H314 resin and therefore formed a completely separate interface between the two phases.

[0203] Example 7 In this embodiment, Heat Set Consider the aging performance of untreated microporous films. Many prior art microporous films have been observed to suffer from property degradation after heat aging (see, for example, Table 1 of U.S. Pat. No. 3,801,404, which shows the progressive loss of nitrogen flux of polypropylene microporous films from 1 to 281 hours at 65° C.; and Table 2 of U.S. Pat. No. 3,843,761, which shows the air flow loss rate of polypropylene microporous films after 1 hour at 90° C.). Heat Set (Polyolefin film at high temperature after stretching) annealing ) have often been used in the prior art (eg, US Pat. No. 3,679,538) to prevent loss of water vapor transmission performance during aging (eg, at 65° C.). Heat Set Untreated PP C7054-07NA MDO microporous films (uniaxially stretched, machine oriented) were aged at 65° C. for various times ranging from 1 hour to 168 hours (Table 10).

[0204] [Table 10]

[0205] As shown in Table 10, the water vapor transmission data did not change significantly over time. In the present invention, as shown by the slight change in the wide-angle X-ray (WAXS) data of the uniaxially oriented (MDO) PP C7054-07NA microporous film before and after stretching (Figures 5A and 5B), the stretching force was consumed to move to the microphase rubber-like (ethylene-propylene copolymer) region and generate a microporous structure. In contrast, for the comparative film, such as the PP TI4020N resin film, the crystal structure rotated and rearranged into a fibrillar structure, and significant orientation was observed in the WAXS data after stretching, with strong diffraction intensity emission in the (110), (040), (130) and (131) planes (Figure 5C before stretching vs. Figure 5D after stretching). This aging performance of the breathable film disclosed herein is due to the following: Heat Set This is distinguished from other homopolymer polyolefin microporous films reported in the prior art, where a high degree of adhesion is always required.

[0206] In addition to the viewpoint of breathability, U.S. Pat. No. 3,843,761 states that Heat Set The same phenomenon of performance degradation after a step was investigated in U.S. Pat. No. 3,843,761: Heat Set The film obtained from the steps is Heat Set The film was compared to a control film that had not undergone the step. Heat Set The flow rate loss due to the steps ranges from 44 to 88% loss relative to the prior art cold draw / single hot draw process; and Heat Set It was concluded that the flow rate loss due to the steps ranged from 24 to 37% loss for their novel cold drawing / multiple successive hot drawing processes.

[0207] As disclosed in U.S. Pat. No. 3,843,761 Heat Set To compare the results, PP C7054-07NA microporous films were produced with the same stretching degree as that disclosed in US Patent No. 3,843,761 (see Table 11). In particular, the first sample, PP C7054-07NA-CS20-HS95, was stretched by 20% cold stretching at 100 mm / s, followed by 95% hot stretching at 5 mm / s and 100°C. The second sample, PP C7054-07NA-CS40-HS75, was stretched by 40% cold stretching at 100 mm / s, followed by 75% hot stretching at 5 mm / s and 100°C.

[0208] [Table 11]

[0209] These microporous films were then subjected to the same Heat Set The relative air permeability is calculated by the following formula:

number

[0210] Table 12 shows the results for 1 hour at 90°C. Heat Set Relative Air Permeability (as defined above) of microporous films comparing pre- and post-Gurley Air Permeability (for each film type, four samples from four positions for each sample, each relative air permeability entry in the table is Heat Set (The ratio is the average of four ratios determined from four measurements at four positions before and after.)

[0211] [Table 12]

[0212] From Table 12, it can be seen that the average relative air permeability is about 1.5 for both oriented films, which is different from the 24-88% flow loss disclosed in U.S. Pat. No. 3,843,761 for the films of the present invention. Heat Set The latter shows an increase in (normal) breathability of about 50%. The porous structure of the polyolefin-based microporous film disclosed in the present invention is Heat Set Can withstand the process.

[0213] The breathable film of the present invention is preferably prepared by subjecting the film to stretching prior to stretching to produce a microporous film. annealing It can be prepared without any step, and furthermore, after pore formation, Heat Set No steps are required. Heat Set If this step is desired for any reason, the films of the present invention may be Heat Set It does not suffer any loss in transparency compared to the film that does not undergo the step.

[0214] Example 8 This example illustrates the performance of PP copolymer biaxially stretched microporous films.

[0215] PP C7054-07NA copolymer film was subjected to simultaneous biaxial stretching, specifically 25% cold stretching at room temperature at a speed of 100 mm / s and 50% hot stretching at 100°C at 5 mm / s. As shown in Table 13, PP C7054-07NA biaxially stretched microporous film has a porosity of 34.7% and an average pore diameter of 44 nm. Correspondingly, the water vapor transmission for this microporous film is about 42 perms (Table 14), and after aging at 65°C for 168 hours, the water vapor transmission increases to 60 perms (Table 14).

[0216] [Table 13]

[0217] [Table 14]

[0218] This example shows that biaxial orientation can also be used to produce microporous films.

[0219] Example 9 To perform a proof-of-concept study of roof membranes, PP C7054-07NA films with a thickness of 762 μm (30 mils) were subjected to a 25% cold stretch (CS) at 100 mm / sec at room temperature, followed by a 100% (150% for the second film) hot stretch (HS) at 5 mm / sec at 100° C. The pore distribution data ranging from tens of nanometers to several microns is shown in FIG. 7. From Table 15, it can be seen that PP C7054-07NA-CS25-HS100 with a thickness of about 660 μm (25.5 mils) has a porosity of 42.5% and gives a water vapor transmission of 58 perms, and PP C7054-07NA-CS25-HS150 with a thickness of about 533 μm (20.6 mils) has a higher porosity of 55% and gives a water vapor transmission of 62 perms.

[0220] [Table 15]

[0221] Useful porosity (e.g., greater than 25%) and permeability values ​​(e.g., greater than 10 perms) are also obtained from thicker 762 μm (30 mil) films, suggesting that the films of the present invention may find utility in breathable roof membranes.

[0222] Example 10 Stretched microporous PP copolymer films were evaluated for medical packaging films and active packaging, where different combinations or degrees of air or water vapor permeability or microbial barrier may be required for each end use. Table 16 shows the film thickness, basis weight, porosity and pore size (average pore diameter) for microporous films obtained from various stretching conditions.

[0223] [Table 16]

[0224] The same series of films were further investigated for permeability properties (Table 17), physical properties (Table 18) and gas fill / empty rates (Table 19) when used as medical packaging.

[0225] Table 17 shows the key barrier properties (Gurley breathability, water vapor transmission and F2638 barrier to microorganisms) obtained for the same microporous films shown in Table 16.

[0226] [Table 17]

[0227] Table 17 shows data for uniaxially stretched PP copolymer films, demonstrating that permeability properties can be modified and controlled by changing stretching conditions. Target ranges for various properties can be estimated by comparison with existing commercial products for these applications (e.g., Tyvek® 1073B or medical grade paper), but these are not strict targets, since there are various end uses for films with different balances of properties (and any one or more of the properties of the commercial products may be significantly above the minimum target range required for that property). At optimized stretching conditions or by using biaxially stretched films (F2638 P max The barrier to microorganisms (as indicated by the values) is already in the commercially viable target range, and a target for Gurley breathability (probably about 10-100 seconds for some applications) should also be available. Some applications may require a specific hydrohead value (resistance to water pressure). As shown in Table 16, the porosity and average pore diameter were measured for films 4-9, and the porosity did not vary significantly (43%-53%), and the pore diameters ranged from 70 nm to 108 nm. Although not shown in the table, films 1-9 had hydrohead values ​​above 500 cmwc (cm of water column), easily exceeding the hydrohead value of Tyvek® 1073B (Hydrohead value of Tyvek® 1073B, about 150 cmwc).

[0228] In addition to permeability properties, breathable films for medical films and active packaging also require suitable physical properties related to film strength such as tensile strength, tear strength and % elongation. Table 18 summarizes such properties for the same series of breathable PP copolymer microporous films.

[0229] [Table 18]

[0230] The orientation process conditions can be modified to control the film's thickness / basis weight as well as other physical properties such as tensile strength, tear strength and elongation, which are important to maintain package integrity during shipping, sterilization and storage, and to ensure that the packaging structure does not tear when the package is peeled open.

[0231] Compared to current technology, at least the tensile strength of these films appears to be sufficient for most medical and active packaging applications.

[0232] Medical packaging currently finds use as a container package that can be filled with a sterilant gas (such as steam or ethylene oxide) to sterilize the package contents (such as a medical device or instrument). The package is filled with the sterilant, the contents then remain with the sterilant gas for a residence time for the sterilization process, and then the gas is vented and the package is sealed with the sterilized device inside. The packaging material provides a barrier against bacteria, microorganisms and particulate matter so as to maintain the sterility of the medical device within the package after sterilization until such device is ready for use.

[0233] Table 19 explores how the stretching process conditions can affect the fill / empty time of PP copolymer films.

[0234] [Table 19]

[0235] In Table 19 above, the improvement in Gurley Air Permeability between the comparative film (immediately after cold stretching) and the inventive film ranges from 45,200 to 860 seconds, which already represents a 20% improvement in the time to fill (or empty) the medical package with gas. To show that even if the relatively modest improvement in Gurley Air Permeability does not match the Gurley Air Permeability of Tyvek® 1073B, it still corresponds to a significant % improvement in the time to fill (or empty) the medical package with gas, which can translate into significant cost savings when such medical packages are used for sterilization of medical instruments and devices, Table 19 also includes hypothetical films, Breathable Film (1) and Breathable Film (2), having Gurley Air Permeability of 300 seconds and 100 seconds, respectively.

[0236] The PP copolymer microporous film described herein is well suited for medical packaging. Compared to current polyethylene technology, the sterilization process can be carried out at higher temperatures due to the higher melting temperature of the PP copolymer film compared to the polyethylene film (e.g., the typical melting temperature of high density polyethylene is about 125-130°C by DSC, whereas the typical melting temperature of the inventive PP-EP copolymer disclosed herein is about 168°C by DSC). Furthermore, the PP copolymer film is easily thermoformed (allowing for easily customizable packaging for various medical devices and instruments) and heat sealable (to easily seal sterilized packs).

[0237] When ranges are used herein with respect to physical properties, such as temperature ranges and pressure ranges, or chemical properties, such as monomer or copolymer content, all combinations and subcombinations of ranges and specific embodiments therein are intended to be included.

[0238] The disclosures of each patent, patent application, and publication cited or described in this specification are hereby incorporated by reference in their entirety.

[0239] Those skilled in the art will understand that many changes and modifications to the preferred embodiments of the present invention may be made and that such changes and modifications may be made without departing from the spirit of the present invention. It is therefore intended that the appended claims cover all such equivalent variations as fall within the true spirit and scope of the present invention.

[0240] Reference Examples A number of PP copolymer films of various thicknesses were extrusion cast onto a chill roll set at a temperature of 80° C. using a 2.5 inch single screw extruder and a 24 inch wide cast die manufactured by Davis-Standard, LLC to produce films with a smooth surface. The base resin is PP C7054-07NA, a polypropylene copolymer available from Braskem American, Inc. (product code C7054-07NA). The extruder was maintained at a constant temperature profile of 460° F. (238° C.) and the chill roll temperature was heated by heated oil. The resulting film thicknesses are summarized in Table 20.

[0241] [Table 20]

[0242] Example 11 The individual film samples in Table 20 were then stretched in the machine direction (MDO - machine direction orientation) using a multi-stage cold stretching process as shown in FIG. 8, where each sample of PP copolymer film from Table 20 was mounted in unwinder section 20, pre-stretch section 23, stretch section 24 and annealing The film was guided through eleven stretching rollers (1-11) comprising section 25 and rewound onto winder section 21. The nip rollers were then closed to apply pressure on the film to prevent slippage during stretching. The roller speed of rollers 3-7 was slowly increased to stretch the film 50% or 100% at 25°C. During the stretching process, the film changed from a translucent color to white, indicating initial pore formation. It was then annealingIn section 25, the cold stretched film is heated at 140°C on rollers 9-11 to fix the pore structure induced by the cold stretching step. The film is then cooled and rewound onto the winder. The measured properties of the final film are summarized in Table 21. The cold stretch degree is defined as (total roller speed ratio-1) x 100%, and the total roll speed ratio is the result of all roller speed ratios (from roller 2 / roller 1 to roller 8 / roller 7) multiplied together.

[0243] [Table 21]

[0244] The MDO cold stretched film was then further hot stretched in the machine direction (MDO) using the same multi-step process as shown in FIG. 8; however, for hot stretching, the process included a pre-hot stretch section 23, a hot stretch section 24 and a annealing Each of the MDO cold stretched films was attached to an unwinder section and guided by eleven stretching rollers before being rewound onto another winder section 21. In this process, the first eight rollers were set to a hot stretch temperature of 135°C. To apply pressure on the film to prevent slippage during stretching, the nip rollers were closed and then the roller speed of rollers 5-8 was slowly increased to stretch the film by 50% or 100% at 135°C. After completion of the hot stretching step, the film was then heated over rollers 9-11 at 140°C to reduce film shrinkage. annealing was carried out. The film was then cooled in the winding machine section 22 and rewound into a roll. The hot stretch degree is defined as (total roller speed ratio-1) x 100%, and the total roll speed ratio is the result of multiplying all the roller speed ratios together (from roller 5 / roller 4 to roller 8 / roller 7). It can be seen from Table 22 that upon completion of the MDO hot stretching, the porosity and average pore diameter of the PP film increased, which results in higher water vapor transmission and lower Gurley air permeability.

[0245] [Table 22]

[0246] Example 12 To illustrate the detrimental effect that hot stretching can have on pore formation and air and water vapor permeability, the above cold and hot stretching processes were applied to a sample of Film 1 that was cold stretched 122% in the machine direction at 25° C. and subsequently hot stretched 103% to 405% in the machine direction. As shown in Table 23, the porosity and permeability of the film worsened with stretching at higher temperatures. As a result, biaxial stretching was proposed to further increase the porosity and pore size, which resulted in higher water vapor permeability and lower Gurley air permeability.

[0247] [Table 23]

[0248] Example 13 A selection of MDO cold and hot stretched films of Example 11 were then placed in a multi-zone oven 50 having an unwind section 41, a preheat section 43, a TDO (transverse orientation) stretching section 44, annealing The film was further hot-stretched in the transverse direction using a process as shown in FIG. 9, including section 45 and cooling section 46. The TDO line has a feed width ranging from 127 mm to 1,016 mm between clips and an exit width range of 203 mm to 2,184 mm between clips to stretch the film in the transverse direction. The TDO clips were capable of holding a wide range of material with film thickness range from 25 μm to 2.54 mm. Following the heated sections (43, 44 and 45) was a 1.5 m long cooling section 46 with circulating outside air. After the TDO oven was preheated to the target temperature (135° C.), the MDO stretched film was attached to the unwinder and led through the feed section of the TDO line. The film was gradually gripped by the clips and pulled through the preheated section at the same width. The film was then stretched in the transverse direction until the TDO target stretch degree was reached. Upon completion of the stretch, the film was cooled to 140° C. annealingsection 45, followed by quenching in cooling area 46 with circulating fresh air. The stretched film was then guided through a stack of rolls and rewound onto winder section 42. To simplify the experiment, the line speed was fixed at 2 m / min. The TDO stretch degree was varied from 50% to 400%. Table 24 shows the stretching conditions and properties of biaxially stretched PP breathable films prepared by MDO cold stretch, MDO hot stretch and TDO hot stretch. All samples had a hydrohead higher than 300. These experiments showed that biaxial stretching is very effective in additional opening of pores in the film. It can be seen from Table 24 that many of the biaxially stretched films have a porosity close to 70% and an average pore diameter larger than 200 nm. Correspondingly, most of the samples have Gurley Air Permeability below 100 sec / 100cc, some in the 20-30 sec / 100cc range, but many have Water Vapor Transmission above 100 perms. At the same time, although not shown in the table, all of the films have Hydroheads above 300 cm, indicating good water resistance. Furthermore, the microbial barrier (%Pmax) as measured by F2638 shows very good results (well within the target range).

[0249] [Table 24]

[0250] Example 14 Table 25 shows the stretching conditions and properties of biaxially stretched PP breathable films prepared by MDO cold stretching followed by TDO hot stretching. Even without MDO hot stretching, very high porosity can be achieved. Also, the porosity and average pore diameter continued to increase with increasing TDO stretching. Correspondingly, these PP breathable films show comparable water vapor transmission, Gurley breathability and microbial barrier.

[0251] [Table 25]

[0252] Example 15 An important property for a waterproof and breathable roof membrane is that it must pass the hydrohead test, resisting 30 meters of water for at least 30 minutes. A selection of stretched films for use as roof membranes was made and tested. As can be seen from Table 26, all samples produced by cold and hot stretching passed the hydrohead test. These MDO samples have film thicknesses ranging from 0.19 mm to 0.53 mm and exhibit water vapor transmission rates (WVTR) ranging from 29.1 perms to 76.7 perms. Biaxially stretched samples produced by cold MDO stretching followed by hot TDO stretching did not pass the hydrohead test due to the more interconnected pores created by the biaxial stretching process.

[0253] [Table 26]

[0254] Example 16 Polypropylene (PP) film samples were produced by cold and hot MDO stretching and tested for use as roof underlayment. All samples shown in Table 27 passed the water resistance (W1), durability after aging (EN 1297 and EN 1296), flexibility at low temperature (≦-20°C) and sideways drop test (TU Berlin). However, it can be seen from Table 27 that samples 16a and 16b had low nail tear strength properties due to low film thickness after stretching. Samples 16c and 16d show that acceptable nail tear strength can be achieved by increasing the film thickness. Samples 16e, 16f and 16g show another possible solution of laminating thinner films with grids or nonwoven films. 16e is laminated to D&L grid, 16f is laminated with Thermanet®, and 16g is laminated to spunbond PP nonwoven, and the property data of these laminates are shown in Table 27. These laminated films demonstrated significant improvement in nail tear strength.

[0255] [Table 27]

[0256] Example 17 Microbial barrier tests were collected on a selection of films from Examples 13 and 14 according to ASTM F2638, along with additional particulate barrier testing with a TSI-8130 automated filter tester. The resulting data are shown in Table 28. Biaxial orientation allows for an increase in porosity and average pore diameter, thus increasing the 100 sec / 100 cm 3 This led to lower Gurley breathability down to less than 0.25%. All biaxially oriented samples showed very good microbial barrier (<0.25%Pmax) within the target range. Furthermore, burst pressure as measured by Hydrohead test was higher than 5 meters for all biaxially oriented PP breathable films.

[0257] [Table 28] (Aspect) (Aspect 1) 1. A microporous polymeric film comprising one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, (i) a polypropylene homopolymer chain segment, the total amount of which is 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segment as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; (ii) ethylene-containing copolymer chain segments in a total amount of 18 to 50% by weight based on the weight of the microporous polymer film or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of at least 45 wt %, based on the weight of the ethylene-containing copolymer chain segment, or at least 55 mol %, based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment. (Aspect 2) 2. The microporous polymer film of claim 1, wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of 45% to 80% by weight based on the weight of the ethylene-containing copolymer chain segment, or 55 mol % to 86 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment. (Aspect 3) The microporous polymer film of claim 1, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 wt. %, based on the weight of the microporous polymer film, or at least 14 mol. %, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 4) The microporous polymer film of embodiment 1, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 weight percent based on the weight of the microporous polymer film, or 14 to 39 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 5) 2. The microporous polymer film of claim 1, wherein the ethylene-containing copolymer chain segment is an ethylene-propylene copolymer chain segment. (Aspect 6) 6. The microporous polymer film of claim 5, wherein the ethylene-propylene copolymer chain segments are random ethylene-propylene copolymer chain segments. (Aspect 7) The microporous polymer film of embodiment 5, wherein the ethylene-propylene copolymer chain segment is an ethylene-propylene diblock copolymer chain segment comprising a polypropylene block and a polyethylene block, or a diblock copolymer chain segment comprising a polypropylene block and an ethylene-propylene copolymer block. (Aspect 8) 8. The microporous polymer film of any one of claims 5 to 7, wherein the one or more ethylene-propylene copolymer chain segments are present in a total amount of 18 to 50 wt % based on the weight of the microporous polymer film or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-propylene copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 9) 8. The microporous polymer film of any one of aspects 5 to 7, wherein at least a portion of the ethylene-propylene copolymer chain segments comprise polymerized units of ethylene in an amount of 45% to 80% by weight based on the weight of the ethylene-propylene copolymer chain segment, or 55 mol % to 86 mol % based on the molar content of polymerized units of ethylene in the ethylene-propylene copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-propylene copolymer chain segment. (Aspect 10) The microporous polymer film of any one of aspects 5 to 8, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 wt.%, based on the weight of the microporous polymer film, or at least 14 mol.%, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 11) The microporous polymer film of any one of aspects 5 to 8, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 wt. % based on the weight of the microporous polymer film, or 14 to 39 mol. % based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 12) 2. The microporous polymer film of embodiment 1, having a porosity of at least 25% and a median pore diameter, 4 V / A, by UOP method 578-11 of at least 25 nm, both characteristics measured by mercury intrusion porosimetry. (Aspect 13) 2. The microporous polymeric film of embodiment 1, having a permeation according to ASTM E96 / E96M-16 in the range of 10 to 150 perms. (Aspect 14) 2. The microporous polymeric film of embodiment 1, further comprising a polypropylene homopolymer. (Aspect 15) 2. The microporous polymeric film of embodiment 1, further comprising an ethylene-containing copolymer. (Aspect 16) 1. A method of forming a microporous polymeric film, the method steps comprising: (a) one or more polypropylene copolymers, (i) one or more polypropylene homopolymer chain segments in a total amount of from 50 to 82 wt % based on the weight of the polypropylene copolymer or from 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer; (ii) one or more ethylene-containing copolymer chain segments in a total amount of from 18 to 50% by weight based on the weight of the polypropylene copolymer or from 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the polypropylene copolymer; providing one or more polypropylene copolymers comprising: at least a portion of said ethylene-containing copolymer chain segments comprising polymerized units of ethylene in an amount of at least 45 wt %, based on the weight of said ethylene-containing copolymer chain segment, or at least 55 mol %, based on the molar content of polymerized units of ethylene in said ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units of said ethylene-containing copolymer chain segment; (b) forming a non-porous film from the polypropylene copolymer or a blend of polymers including the polypropylene copolymer; (c) removing the non-perforated film by (i) at least one cold drawing step at a temperature in the range of -20°C to 50°C; and (ii) at least one hot-drawing step at a temperature in the range of 50°C to 150°C and subjecting the resulting film to successive cold and hot stretching steps, thereby producing a microporous polymer film. A method comprising: (Aspect 17) 17. The method of embodiment 16, wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of 45% to 80% by weight based on the weight of the ethylene-containing copolymer chain segment, or 55 mol % to 86 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment. (Aspect 18) The method of claim 16, wherein the microporous polymer film has a total ethylene content in polymerized form of at least 10 wt.%, based on the weight of the microporous polymer film, or at least 14 mol.%, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 19) 17. The method of claim 16, wherein the microporous polymer film has a total ethylene content in polymerized form of 10 to 30 weight percent based on the weight of the microporous polymer film, or 14 to 39 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 20) The method of embodiment 16, wherein the ethylene-containing copolymer chain segment is an ethylene-propylene copolymer chain segment. (Aspect 21) 21. The method of embodiment 20, wherein the ethylene-propylene copolymer chain segments are random ethylene-propylene copolymer chain segments. (Aspect 22) 21. The method of embodiment 20, wherein the ethylene-propylene copolymer chain segment is an ethylene-propylene diblock copolymer chain segment comprising a polypropylene block and a polyethylene block, or a diblock copolymer chain segment comprising a polypropylene block and an ethylene-propylene copolymer block. (Aspect 23) 23. The method of any one of aspects 20-22, wherein the ethylene-propylene copolymer chain segments are present in a total amount of from 18 to 50 weight % based on the weight of the polypropylene copolymer or from 21 to 57 mole % based on the molar content of polymerized monomer units in the ethylene-propylene copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the propylene copolymer. (Aspect 24) 24. The method of any one of aspects 20-23, wherein at least a portion of the ethylene-propylene copolymer chain segments comprise polymerized units of ethylene in an amount of 45% to 80% by weight based on the weight of the ethylene-propylene copolymer chain segment, or 55 mol % to 86 mol % based on the molar content of polymerized units of ethylene in the ethylene-propylene copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-propylene copolymer chain segment. (Aspect 25) 24. The method of any one of aspects 20-23, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 wt.%, based on the weight of the microporous polymer film, or at least 14 mol.%, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 26) 24. The method of any one of aspects 20 to 23, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 wt. %, based on the weight of the microporous polymer film, or 14 to 39 mol. %, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film. (Aspect 27) The polypropylene copolymer has a melt flow rate, measured according to ASTM D-1238, condition L, at 230° C. and 2.16 kg, of 0.1 to 100 g / 10 min, and a melt flow rate of 0.9 g / cm 3 17. The method of embodiment 16, wherein the densification is greater than 100%. (Aspect 28) 17. The method of embodiment 16, wherein the polypropylene copolymer is blended with a polypropylene homopolymer to form a polymer blend prior to forming the non-perforated film. (Aspect 29) 17. The method of embodiment 16, wherein the polypropylene copolymer is blended with an ethylene-containing copolymer to form a polymer blend prior to forming the non-perforated film. (Aspect 30) 17. The method of embodiment 16, wherein forming the non-porous film is accomplished by extruding the polypropylene copolymer or polymer blend thereof in a melt state. (Aspect 31) 17. The method of claim 16, wherein the nonporous polymeric film has a morphology characterized by a majority polymer phase of polypropylene, a plurality of minor polymer domains of an ethylene-containing copolymer within the majority polymer phase, and inclusions of a predominant polypropylene phase within the minor polymer domains. (Aspect 32) 17. The method of embodiment 16, wherein the method is performed without any annealing step after formation of the non-porous film. (Aspect 33) 17. The method of embodiment 16, wherein the at least one cold stretching step stretches the film by at least 10% in at least one direction, and the at least one hot stretching step stretches the film by at least 20% in at least one direction. (Aspect 34) 17. The method of embodiment 16, carried out without any annealing or heat-setting step after forming the microporous polymeric film and before step (c). (Aspect 35) 17. The method of embodiment 16, which is a continuous process for producing a microporous polymeric film. (Aspect 36) 17. The method of embodiment 16, wherein the microporous polymer film has a porosity of at least 25% and a median pore diameter of at least 25 nm (4V / A, by UOP method 578-11), both characteristics measured by mercury intrusion porosimetry. (Aspect 37) 17. The method of embodiment 16, wherein the microporous polymeric film has a permeability according to ASTM E96 / E96M-16 in the range of 10 to 150 perms. (Aspect 38) A microporous polymer film formed by the method of any one of embodiments 16 to 37. (Aspect 39) A microporous polymer film formed by the method of any one of claims 16 to 37, wherein the nonporous polymer film has a morphology characterized by a majority polymer phase of polypropylene, a plurality of minor polymer domains of an ethylene-containing copolymer within the majority polymer phase, and inclusion phases of a predominant polypropylene phase within the minor polymer domains. (Aspect 40) 2. The microporous polymeric film of embodiment 1, which is a roof membrane or a component thereof. (Aspect 41) 41. The microporous polymeric film of embodiment 40, having a thickness of at least 100 μm. (Aspect 42) 2. The microporous polymeric film of embodiment 1, which is at least a part of a medical packaging or active packaging article or a medical back table cover. (Aspect 43) A medical packaging or active packaging article or a medical back table cover comprising the microporous polymeric film according to any one of aspects 1 to 15. (Aspect 44) A medical packaging or active packaging article or medical back table cover comprising a microporous polymeric film, the microporous polymeric film comprising one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the microporous polymeric film comprising: (i) a polypropylene homopolymer chain segment, the total amount of which is 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segment as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; (ii) ethylene-containing copolymer chain segments in a total amount of 18 to 50% by weight based on the weight of the microporous polymer film or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; wherein at least a portion of the ethylene-containing copolymer chain segments comprise polymerized units of ethylene in an amount of at least 45% by weight, based on the weight of the ethylene-containing copolymer chain segment, or at least 55 mol %, based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment. (Aspect 45) 45. The medical packaging or active packaging article or medical back table cover of claim 44, wherein the microporous polymeric film has a barrier against microorganisms of <10%, equivalent to the maximum penetration defined by ASTM F2638-18, calculated %Pmax. (Aspect 46) The microporous polymer film has a melting point of 1 to 35,000 seconds / 100 cm 3 45. The medical packaging or active packaging article or medical back table cover of claim 44, having a Gurley Gauge Air Permeability of 0.01% or less and controlling the inflow or outflow of air or one or more gases into or out of the package. (Aspect 47) 47. The medical packaging or active packaging article or medical back table cover of claim 46, wherein the microporous polymeric film is thermoformable and heat sealable. (Aspect 48) A microporous polymeric film comprising a polypropylene copolymer made from the reaction product of a polypropylene homopolymer and an ethylene-propylene copolymer.

Claims

1. 1. A microporous polymeric film comprising one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, (i) polypropylene homopolymer chain segments in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; (ii) ethylene-containing copolymer chain segments in a total amount of 18 to 50 weight percent based on the weight of said microporous polymer film or 21 to 57 mole percent based on the molar content of polymerized monomer units in said ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in said microporous polymer film; at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of at least 45 wt %, based on the weight of the ethylene-containing copolymer chain segment, or at least 55 mol %, based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment; A microporous polymer film having a porosity of at least 25% and a median pore diameter, 4 V / A, by UOP method 578-11 of at least 25 nm, both characteristics measured by mercury intrusion porosimetry.

2. 2. The microporous polymer film of claim 1, wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of 45% to 80% by weight based on the weight of the ethylene-containing copolymer chain segment or 55 mol % to 86 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment.

3. 2. The microporous polymer film of claim 1, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 wt. %, based on the weight of the microporous polymer film, or at least 14 mol. %, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

4. 2. The microporous polymer film of claim 1, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 weight percent based on the weight of the microporous polymer film, or 14 to 39 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

5. 2. The microporous polymeric film of claim 1, wherein the ethylene-containing copolymer chain segment is an ethylene-propylene copolymer chain segment.

6. 6. The microporous polymeric film of claim 5, wherein the ethylene-propylene copolymer chain segments are random ethylene-propylene copolymer chain segments.

7. 6. The microporous polymer film of claim 5, wherein the ethylene-propylene copolymer chain segment is an ethylene-propylene diblock copolymer chain segment comprising a polypropylene block and a polyethylene block, or a diblock copolymer chain segment comprising a polypropylene block and an ethylene-propylene copolymer block.

8. The microporous polymer film of any one of claims 5 to 7, wherein the one or more ethylene-propylene copolymer chain segments are present in a total amount of 18 to 50 wt % based on the weight of the microporous polymer film or 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-propylene copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

9. 8. The microporous polymer film of any one of claims 5 to 7, wherein at least a portion of the ethylene-propylene copolymer chain segments comprise polymerized units of ethylene in an amount of 45% to 80% by weight based on the weight of the ethylene-propylene copolymer chain segment or 55 mol% to 86 mol% based on the molar content of polymerized units of ethylene in the ethylene-propylene copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-propylene copolymer chain segment.

10. The microporous polymer film of any one of claims 5 to 8, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 wt% based on the weight of the microporous polymer film, or at least 14 mol% based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

11. The microporous polymer film of any one of claims 5 to 8, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 wt% based on the weight of the microporous polymer film, or 14 to 39 mol% based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

12. 10. The microporous polymeric film of claim 1 having a permeation according to ASTM E96 / E96M-16 in the range of 10 to 150 perms.

13. 10. The microporous polymeric film of claim 1 further comprising a polypropylene homopolymer.

14. 10. The microporous polymeric film of claim 1 further comprising an ethylene-containing copolymer.

15. 1. A method of forming a microporous polymeric film, the method steps comprising: (a) one or more polypropylene copolymers, (i) one or more polypropylene homopolymer chain segments in a total amount of from 50 to 82 wt % based on the weight of the polypropylene copolymer or from 43 to 79 mol % based on the molar content of polymerized units of propylene in said polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in said polypropylene copolymer; (ii) one or more ethylene-containing copolymer chain segments in a total amount of from 18 to 50% by weight based on the weight of the polypropylene copolymer or from 21 to 57 mol % based on the molar content of polymerized monomer units in the ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in said polypropylene copolymer; providing one or more polypropylene copolymers comprising: at least a portion of said ethylene-containing copolymer chain segments comprising polymerized units of ethylene in an amount of at least 45 wt %, based on the weight of said ethylene-containing copolymer chain segment, or at least 55 mol %, based on the molar content of polymerized units of ethylene in said ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units of said ethylene-containing copolymer chain segment; (b) forming a non-porous film from the polypropylene copolymer or a blend of polymers including the polypropylene copolymer; (c) the non-porous film, (i) at least one cold drawing step at a temperature in the range of -20°C to 50°C; and (ii) at least one hot stretching step at a temperature in the range of 50° C. to 150° C. and subjecting the resulting film to successive cold and hot stretching steps, thereby producing a microporous polymer film. A method comprising:

16. 16. The method of claim 15, wherein at least a portion of the ethylene-containing copolymer chain segment comprises polymerized units of ethylene in an amount of from 45% to 80% by weight based on the weight of the ethylene-containing copolymer chain segment or from 55 mol % to 86 mol % based on the molar content of polymerized units of ethylene in the ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in the ethylene-containing copolymer chain segment.

17. 16. The method of claim 15, wherein the microporous polymer film has a total ethylene content in polymerized form of at least 10 weight percent based on the weight of the microporous polymer film, or at least 14 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

18. 16. The method of claim 15, wherein the microporous polymer film has a total ethylene content in polymerized form of 10 to 30 weight percent based on the weight of the microporous polymer film, or 14 to 39 mole percent based on the molar content of polymerized units of ethylene in the microporous polymer film as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

19. The method of claim 15, wherein the ethylene-containing copolymer chain segment is an ethylene-propylene copolymer chain segment.

20. 20. The method of claim 19, wherein the ethylene-propylene copolymer chain segments are random ethylene-propylene copolymer chain segments.

21. 20. The method of claim 19, wherein the ethylene-propylene copolymer chain segment is an ethylene-propylene diblock copolymer chain segment comprising a polypropylene block and a polyethylene block, or a diblock copolymer chain segment comprising a polypropylene block and an ethylene-propylene copolymer block.

22. 22. The method of any one of claims 19 to 21, wherein the ethylene-propylene copolymer chain segments are present in a total amount of 18 to 50 weight % based on the weight of the polypropylene copolymer or 21 to 57 mole % based on the molar content of polymerized monomer units in the ethylene-propylene copolymer chain segments as a percentage of the total molar content of polymerized monomer units in the propylene copolymer.

23. 23. The method of any one of claims 19 to 22, wherein at least a portion of the ethylene-propylene copolymer chain segments comprise polymerized units of ethylene in an amount of from 45% to 80% by weight, based on the weight of the ethylene-propylene copolymer chain segment, or from 55 mol % to 86 mol %, based on the molar content of polymerized units of ethylene in the ethylene-propylene copolymer chain segment, as a percentage of the total molar content of polymerized monomer units in the ethylene-propylene copolymer chain segment.

24. 23. The method of any one of claims 19 to 22, wherein the total ethylene content in polymerized form in the microporous polymer film is at least 10 wt%, based on the weight of the microporous polymer film, or at least 14 mol%, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

25. 23. The method of any one of claims 19 to 22, wherein the total ethylene content in polymerized form in the microporous polymer film is 10 to 30 wt%, based on the weight of the microporous polymer film, or 14 to 39 mol%, based on the molar content of polymerized units of ethylene in the microporous polymer film, as a percentage of the total molar content of polymerized monomer units in the microporous polymer film.

26. The polypropylene copolymer has a melt flow rate, measured according to ASTM D-1238, Condition L at 230° C. and 2.16 kg, of 0.1 to 100 g / 10 min, and a melt flow rate of 0.9 g / cm 3 The method of claim 15, wherein the granular material has a density greater than 100%.

27. 16. The method of claim 15, wherein the polypropylene copolymer is blended with a polypropylene homopolymer to form a polymer blend prior to forming the non-perforated film.

28. 16. The method of claim 15, wherein the polypropylene copolymer is blended with an ethylene-containing copolymer to form a polymer blend prior to forming the non-perforated film.

29. 16. The method of claim 15, wherein forming the non-porous film is accomplished by extruding the polypropylene copolymer or polymer blend thereof in a melt state.

30. 16. The method of claim 15, wherein the non-porous polymeric film has a morphology characterized by a majority polymer phase of polypropylene, a plurality of minor polymer domains of an ethylene-containing copolymer within the majority polymer phase, and inclusions of a predominant polypropylene phase within the minor polymer domains.

31. The method of claim 15 , performed without any annealing step after formation of the non-porous film.

32. 16. The method of claim 15, wherein the at least one cold stretching step stretches the film by at least 10% in at least one direction and the at least one hot stretching step stretches the film by at least 20% in at least one direction.

33. 16. The method of claim 15, carried out without any annealing or heat setting step after forming the microporous polymeric film and before step (c).

34. 16. The method of claim 15 which is a continuous process for producing a microporous polymeric film.

35. 16. The method of claim 15, wherein the microporous polymer film has a porosity of at least 25% and a median pore diameter of at least 25 nm (4V / A, by UOP method 578-11), both characteristics measured by mercury intrusion porosimetry.

36. The method of claim 15, wherein the microporous polymeric film has a permeability according to ASTM E96 / E96M-16 ranging from 10 to 150 perms.

37. A microporous polymeric film formed by the method of any one of claims 15 to 36.

38. 37. A microporous polymer film formed by the method of any one of claims 15 to 36, wherein the non-porous polymer film has a morphology characterized by a majority polymer phase of polypropylene, a plurality of minor polymer domains of an ethylene-containing copolymer within the majority polymer phase, and inclusion phases of a predominant polypropylene phase within the minor polymer domains.

39. 10. The microporous polymeric film of claim 1 which is or is a component of a roof membrane.

40. 40. The microporous polymeric film of claim 39 having a thickness of at least 100 μm.

41. 10. The microporous polymeric film of claim 1, which is at least a portion of a medical packaging or active packaging article or a medical back table cover.

42. A medical packaging or active packaging article or a medical back table cover comprising the microporous polymeric film of any one of claims 1 to 14.

43. A medical packaging or active packaging article or medical back table cover comprising a microporous polymeric film, the microporous polymeric film comprising one or more polypropylene copolymers comprising one or more polypropylene homopolymer chain segments and one or more ethylene-containing copolymer chain segments, the microporous polymeric film comprising: (i) polypropylene homopolymer chain segments in a total amount of 50 to 82 wt % based on the weight of the microporous polymer film or 43 to 79 mol % based on the molar content of polymerized units of propylene in the polypropylene homopolymer chain segments as a percentage of the total molar content of polymerized monomer units in the microporous polymer film; (ii) ethylene-containing copolymer chain segments in a total amount of 18 to 50 weight percent based on the weight of said microporous polymer film or 21 to 57 mole percent based on the molar content of polymerized monomer units in said ethylene-containing copolymer chain segments as a percentage of the total molar content of polymerized monomer units in said microporous polymer film; wherein at least a portion of said ethylene-containing copolymer chain segments comprise polymerized units of ethylene in an amount of at least 45% by weight, based on the weight of said ethylene-containing copolymer chain segment, or at least 55 mol %, based on the molar content of polymerized units of ethylene in said ethylene-containing copolymer chain segment as a percentage of the total molar content of polymerized monomer units in said ethylene-containing copolymer chain segment.

44. 44. The medical packaging or active packaging article or medical back table cover of claim 43, wherein the microporous polymeric film has a barrier to microorganisms equivalent to the maximum penetration, calculated %Pmax, defined by ASTM F2638-18, of <10%.

45. The microporous polymer film has a viscosity of 1 to 35,000 seconds / 100 cm 3 44. The medical packaging or active packaging article or medical back table cover of claim 43, having a Gurley Gauge Air Permeability of at least 100% and controlling the inflow or outflow of air or one or more gases into or out of the package.

46. 46. ​​The medical packaging or active packaging article or medical back table cover of claim 45, wherein said microporous polymeric film is thermoformable and heat sealable.

Citation Information

Patent Citations

  • Propylenic block copolymer

    JP2003206325A

  • Propylene-based resin composition and its application

    JP2009084303A

  • Heat resistant polyolefin microporous film and manufacturing method therefor

    JP2016023307A